QCGN Asks New Parliament to Deliver Improved Official Languages Act - Quebec Community Groups Network (QCGN) (2019)
Keywords: Official Language Minority Community (OLMC)

Report on Hearings on Bill 40 Organized by APPELE-Québec - Alliance for the Promotion of Public English-language Education in Quebec (APPELE-Quebec) (2019)
APPELE-Québec heard from 18 groups and individuals at hearings it sponsored on Bill 40; An Act to amend mainly the Education Act with regard to school organization and governance. We benefited from the input of a wide cross-section of representatives from Quebec’s English-speaking community as well as from concerned parties from across Canada.

QCGN Asks Government to Exclude English School Boards from Education Reform Plan - Quebec Community Groups Network (QCGN) (2019)

Response to Bill 40 : An Act to Amend Mainly the Education Act with Regard to School Organization - Quebec Federation of Home and School Associations (QFHSA) (2019)
On October 1, 2019, the CAQ Minister of Education and Higher Education Jean Francois Roberge tabled Bill 40, An Act to amend mainly the Education Act with regard to school organization and governance, fulfilling an election promise made by Premier Francois Legault to abolish school boards in Quebec. This lengthy and complex projet de loi affects more than 84 separate acts and regulations and we feel, proposes a governance model that is unnecessarily complex and unmanageable.

Black and English-speaking in Montreal : an Intersectional Snapshot - Zehavi, Bonnie (Collaborative Unity and Existential Responsibility, 2019)
This paper presents a general overview of the challenges faced by English-speaking Black community members in Montreal, as well as the exacerbation of those barriers for individuals with a history of justice involvement. Frontline community initiatives focusing on education, employment, and entrepreneurship at DESTA Black Youth Network are profiled as an example of grassroots efforts to mitigate disparate circumstances between English-speaking Black Montrealers and their white counterparts. Statistical data in the areas of educational attainment, rates of unemployment, and income provide the platform for analysis and, recognizing the multiple identity experiences of belonging to a racialized and linguistic minority, an intersectional framework is employed. Recommendations for more race-based study, policy, and funding to better support equity strategies are provided.
Keywords: Official Language Minority Community (OLMC)

Special Consultations on Bill 40 : An Act to Amend Mainly the Education Act with Regard to School Organization and Governance - Quebec Community Groups Network (QCGN) (2019)
The Quebec Community Groups Network (“QCGN”) has not been invited to appear before the Committee in the course of its special consultations on Bill 40. Nonetheless, the QCGN submits this brief to the Committee. In addition to providing an excellent education to students, Quebec’s English public schools exist to preserve and promote the language and unique culture of English-speaking Quebec. The Government of Quebec must recognize and support the linguistic and cultural rights of Quebec’s English-speaking community. At the same time, the English-speaking community of Quebec recognizes the need for reforms. In 2015, the community conducted a wide-ranging consultation, and prepared recommendations to the Minister of Education and Higher Education on the matter. Bill 40 largely ignores those recommendations, particularly the recommendations for improving the electoral system. It does not reflect a model of education governance by and for the English- speaking community.
Keywords: Official Language Minority Community (OLMC)

Access Programs for Health and Social Services in the English Language : Presentation to NPIs - Prata, Ghislaine (2019)

QCGN Board Responds to Public Withdrawal of Board Members - Quebec Community Groups Network (QCGN) (2019)

Quebec Community Groups Network Brief to Committee on Culture and Education : Special Consultations on Bill 40: An Act to amend mainly the Education Act with regard to school organization and governance - Quebec Community Groups Network (QCGN) (2019)
The Quebec Community Groups Network (“QCGN”) has not been invited to appear before the Committee in the course of its special consultations on Bill 40. Nonetheless, the QCGN submits this brief to the Committee. In addition to providing an excellent education to students, Quebec’s English public schools exist to preserve and promote the language and unique culture of English-speaking Quebec. Schools are key and central institutions of the English-speaking community of Quebec. The Government of Quebec must recognize and support the linguistic and cultural rights of Quebec’s English-speaking community. Management and control of our educational institutions cannot be unilaterally restricted. At the same time, the English-speaking community of Quebec recognizes the need for reforms to the governance of its educational institutions.
Keywords: Official Language Minority Community (OLMC)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2019)

Baseline Data Report 2018-2019 Part 1 (Telephone Survey) : English-language Health and Social Services Access in Québec - Pocock, Joanne (Community Health and Social Services Network, 2019)
The Baseline Data Report series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2018-2019 explores a single factor that is a key determinant of the health of English-speaking Quebec, namely, access to health and social services.

Baseline Data Report 2018-2019 Part 2 (Focus Groups) : English-language Health and Social Services Access in Québec - Pocock, Joanne (Community Health and Social Services Network, 2019)
The CHSSN focus groups were designed as face-to-face group discussions with a lead moderator. As the accompanying table indicates, nine focus groups were held across six regions with a total attendance of 116 English speakers (18+). The recruitment process entailed a public announcement by the host organizations located in each region: Neighbours Regional Association of Rouyn-Noranda (NRARN), English Community Organization in Saguenay-Lac-St-Jean (ECO-02), North Shore Community Association (NSCA), Coasters Association (Coasters), Megantic Community Development Corporation (MCDC), and the Centre for Access to Services in English (CASE). The host organizations in each region also assumed responsibility for arranging a time, finding a location, providing refreshments and technical assistance.

[Letter to members regarding the withdrawal of QCGN board members] - Quebec Community Groups Network (QCGN) (2019)
Keywords: Official Language Minority Community (OLMC)

QCGN Laments Loss of Some Network Members - Quebec Community Groups Network (QCGN) (2019)
Keywords: Official Language Minority Community (OLMC)

QCGN Wants New Parliament to Ensure Respect for English and French as the Official Languages of Canada - Quebec Community Groups Network (QCGN) (2019)
Keywords: Official Language Minority Community (OLMC)

Employment of English Speakers in Quebec's Public Service - Cooper, Celine; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2019)
This document provides background information related to the participation of English speakers in Quebec’s Public Service (QPS). The first section synthesizes information from relevant primary and secondary sources. The second section includes summaries of preliminary discussions with key informants, as well as our observations.
Keywords: Official Language Minority Community (OLMC)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2019)

QCGN Intervienes in B.C. School Board Case at Supreme Court of Canada - Quebec Community Groups Network (QCGN) (2019)
Keywords: Official Language Minority Community (OLMC)

English-speaking Quebecers Shows High Levels of Distrust with Coalition Avenir Québec Government - Quebec Community Groups Network (QCGN) (2019)

Annual Report 2018-2019 - Community Health and Social Services Network (CHSSN) (2019)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2019)

Bright Beginnings Project Descriptions - Community Health and Social Services Network (CHSSN) (2019)

Third Civic Engagement Forum for Quebec's English-speaking Youth Kicks off at Bishop's University this Weekend - The Bishop's Forum (2019)

Bishop's Forum Bringing Young Leaders Together - The Record (2019)

VEQ’s Summer 2019 Newsletter - Voice of English-speaking Quebec (VEQ) (2019)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2019)

QCGN Expresses Serious Misgivings About Vague Government Consultation Plan - Quebec Community Groups Network (QCGN) (2019)

Community Education and Development : Perspectives on Employment, Employability and Development of English-Speaking Black Minority of Quebec - Bayne, Clarence S (Collaborative Unity and Existential Responsibility, 2019)
On December 7, 2018, the Black Community Forum of Montreal held a conference on “Community Education and Development: perspectives on English-Speaking Blacks and Other Minorities”. The IJCDMS Journal has selected a number of the conference papers for publication in its Special Conference Series: “Collaborative Unity and Existential Responsibility.” This article serves as an overview to the conference; and provides a theoretical framework against which the reader can derive a better understanding of those papers. It allows the reader to reflect meaningfully on the optimality of the decision search rules adopted by various cultural subgroups, by comparing them to the behaviors of successful agent types in the computer simulated studies discussed in this paper. The targeted cultural sub-populations are the English-Speaking Blacks in Montreal.
Keywords: Official Language Minority Community (OLMC)

Reply by QCGN President Geoffrey Chambers to Mathieu Bock-Côté's column La trahison published in Le Journal de Montréal on July 6, 2019 - Chambers, Geoffrey (2019)
Keywords: Official Language Minority Community (OLMC)

Memorandum of Understanding Between Acadians in New Brunswick, English-speaking Quebecers and Franco-Ontarians - Société de l’Acadie du Nouveau-Brunswick (SANB); Quebec Community Groups Network (QCGN); Assemblée de la francophonie de l’Ontario (AFO) (2019)
Keywords: Official Language Minority Community (OLMC)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2019)

QCGN wraps up 24th Annual General Meeting Prepared to Face Government Threats - Quebec Community Groups Network (QCGN) (2019)
Keywords: Official Language Minority Community (OLMC)

English-speaking fathers in Quebec exposed to greater vulnerability - Community Health and Social Services Network (CHSSN) (2019)

English-speaking Fathers in Quebec Exposed to Greater Vulnerability - Community Health and Social Services Network (CHSSN) (2019)

Practice Makes Perfect - Voice of English-speaking Quebec (VEQ) (2019)

QCGN Supports Commissioner's Call for a More Effective Official Languages Act - Quebec Community Groups Network (QCGN) (2019)
Keywords: Official Language Minority Community (OLMC)

The South Shore of Montérégie-Centre : Towards a Portrait of the English-speaking Community - Assistance and Referral Centre (ARC); Richardson, Mary (2019)

2018-2019 Annual Report - Voice of English-speaking Quebec (VEQ) (2019)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2019)

Community Unites to Fight for Domocratically Elected School Boards - Alliance for the Promotion of Public English-language Education in Quebec (APPELE-Quebec) (2019)

Caractéristiques sociodémographiques de la population anglophone de Laval - L’Association amicale des jeunes et parents AGAPE Inc. (AGAPE, 2019)
Ce document a été créé par l’Association amicale des jeunes et parents AGAPE Inc. par l’entremise de l’Initiative de réseautage et de partenariats (IRP) du Réseaux communautaire de santé et de services sociaux (RCSSS) qui appuie le développement et la mobilisation des réseaux communautaires de santé et de services sociaux partout au Québec afin de collaborer avec des partenaires locaux et régionaux dans le but d’améliorer l’accès à la santé et aux services sociaux pour la population anglophone minoritaire.

Report on the Consultation with the English-speaking Seniors of Laval - Pocock, Joanne (AGAPE, 2019)
This report was done in anticipation of the Laval Regional Access Committee who’s mandate is to give advice on the health and social services access program developed by the Centre intégré de santé et de services sociaux de Laval (CISSS Laval) in accordance with sections 348 and 510 of the Act respecting health and social services. The Regional Access Committee evaluates the access program and, if necessary, suggests modifications. The committee provides an opinion on the modalities of application, monitoring and evaluation of the regional access program. Additionally, the committee gives an opinion to the CISSS de Laval on the priority needs of the region’s English-speaking clientele in terms of accessibility to health and social services in the English language. Finally, the committee makes recommendations regarding promotional and awareness activities related to accessibility of services in the English language.

Quebec Past and Present : 7th Colloquium on Quebec Studies - Eastern Townships Resource Centre (ETRC); Bishop's University; State University of New York Plattsburgh (2019)

QCGN Pleased with Renewed Support for English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2019)
Keywords: Official Language Minority Community (OLMC)

QCGN Eager to Contribute to Hearings on Modernization of the Official Languages Act - Quebec Community Groups Network (QCGN) (2019)
Keywords: Official Language Minority Community (OLMC)

Assessment of the Priority Setting Process for the English-speaking Communities of Quebec (ESCQ) : Guide for the Focus Groups - Canada. Department of Canadian Heritage; Quebec Community Groups Network (QCGN); KSAR & Associates (2019)

VEQ’s Spring 2019 Newsletter - Voice of English-speaking Quebec (VEQ) (2019)

Needs Assessment Report: Providing Resources, Networks, and Representation for English-speaking Youth in Quebec - Youth for Youth Québec (Y4Y Québec) (2019)
Keywords: Official Language Minority Community (OLMC)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2019)

QCGN Calls on Premier Legault to Support English-speaking Community - Quebec Community Groups Network (QCGN) (2019)

Shutdown of Riverdale Destabilizing and Ill-advised : QCGN - Quebec Community Groups Network (QCGN) (2019)
Keywords: Official Language Minority Community (OLMC)

QCGN Begs to Differ on Premier's Interpretation of English Signage in Hospitals - Quebec Community Groups Network (QCGN) (2019)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2019)

Survey on Access to Health Care and Social Services for the English-speaking Community of Laval - AGAPE (2019)

Evaluating the Impact of BIll 101 on the English-speaking Communities of Quebec - Bourhis, Richard Y. (Language Problems and Language Planning, 2019)

Community NetLink - Community Health and Social Services Network (CHSSN) (2019)

Community NetLink - Community Health and Social Services Network (CHSSN) (2019)

Who Are Our 0-5 year Olds? : A Portrait of English-speaking 0-5 Year Olds in the Outaouais Region WHO AREOER - Connexions Resource Centre (2019)

ELAN 15 Year Anniversary Booklet - English Language Arts Network (ELAN) (2019)

Community Mobilization Model for Improving the Health and Vitality of English-Speaking Communities in Quebec - Kueber, Russell (Community Health and Social Services Network (CHSSN), 2019)
This brief description of a "Community Mobilization Model for Improving the Health and Vitality of English-speaking Communities in Quebec" includes a condensed background of English-speaking communities. It also includes a short description of some key concepts used in the model. The model is designed to communicate the approach taken by community helath and social services networks, which positions them as drivers of change in mobilizing English-speaking communities.

Laurentian English Services Advisory Network - LESAN (2019)

Innovation in Action / Innovation en action - Quebec Community Groups Network (QCGN) (2019)
The Community Innovation Fund (CIF) has helped Quebec’s English- speaking communities transform social innovation into action through the development of skills. The Fund financed 10 innovative projects that targeted particular needs and priorities of vulnerable English-speaking youth, seniors and newcomers. Each project, in its own way, served to improve job skills or help maintain basic socio-economic security of English-speaking Quebecers. In the following pages, you will learn more about these projects – what they set out to do, what they’ve accomplished and how they served to enhance the vitality of English-speaking Quebec.
Keywords: Official Language Minority Community (OLMC)

Strategic Priorities Forum : 2018 – 2019 Priorities of the English-speaking Community of Quebec and Annual Report of the Priority Setting Steering Committee - Quebec Community Groups Network (QCGN) (2019)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2019)

Annual Report : 2018-2019 - Réseau de l’est de l’île pour les services en anglais (REISA) (2019)

Employability Initiatives : 2019-2021 - Réseau de l’est de l’île pour les services en anglais (REISA) (2019)

Health and Social Service Resources for English-Speaking Communities in the East and North of Montreal : 2019-2020 - Réseau de l’est de l’île pour les services en anglais (REISA) (2019)

Health and Social Service Resources for the English-speaking Seniors in the East end of Montreal - Réseau de l’est de l’île pour les services en anglais (REISA) (2019)

Annual Report 2018-19 - The English Speaking Catholic Council (ESCC) (2019)

Annual Report 2018-2019 - Youth for Youth Québec (Y4Y Québec) (2019)

QCGN Mourns Loss of James Shea, Educator and Advocate for Linguistic Duality - Quebec Community Groups Network (QCGN) (2018)

English-speaking Community Will Not Abandon School Boards, QCGN Advises Premier - Quebec Community Groups Network (QCGN) (2018)

English-speaking Blacks in Quebec : Highlights from the 2016 Census - Floch, William (Conference on Community Education and Development : Perspectives on English-speaking Blacks and Other Minorities, 2018)

Y4Y Quebec Opposes the Cancellation of the French-language University in Ontario and Expresses its Solidarity with the Young Franco-Ontarians Who Worked on the Project - Youth for Youth Québec (Y4Y Québec) (2018)

QCGN Denounces Cuts to French Language Services in Ontario - Quebec Community Groups Network (QCGN) (2018)
Keywords: Official Language Minority Community (OLMC)

[Letter to René Cormier, Chair of the Senate Standing Committee on Official Languages, from Geoffrey Chambers, QCGN President, re: the Official Languages Act] - Chambers, Geoffrey (2018)

English-speaking Communities of the Gaspésie – Îles-de-la-Madeleine: A Regional Profile - Richardson, Mary; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)

English-speaking Communities of the Gaspésie-Îles-de-la-Madeleine : A Regional Profile - Vision Gaspé-Percé Now (VGPN) (2018)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2018)

Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)

Report on the First "Minority Community Vitality Through Education" Forum - Cooper, Celine; Donovan, Patrick; O'Donnell, Lorraine (Quebec English-speaking Communities Research Network (QUESCREN), 2018)
From October 28 to 30, 2018, researchers, practitioners, community stakeholders and policymakers gathered at Concordia University for a three-day forum entitled “Minority Community Vitality Through Education,” and focused on Quebec’s English-speaking minority population. The Forum was convened by the Inter-Level Educational Table, a committee of the Quebec English-Speaking Communities Research Network (QUESCREN) at Concordia University. The objective of the Forum was to encourage mobilization around the development of a healthy and sustainable English-language educational offer in Quebec, from pre-K to university, that leads to student retention, access to good jobs in Quebec and a strong sense of identity and belonging.
Keywords: Official Language Minority Community (OLMC)

Secondary School Exchanges : A Promising Way of Fostering Bilingualism in the Next Generation - Lai, Edward; Orme, Charlie; Fleming, Scott (Y4Y Québec, 2018)
In Quebec, it is a basic fact that a solid grasp of the French language is essential to finding work, participating fully in the political process, and integrating into society. While statistics show that bilingualism is very common among the Englishspeaking minority, and especially so among youth, problems nonetheless arise. Young English-speakers frequently report that they do not feel confident enough in their ability to speak French, while others remark that their written French is not strong enough to land a job. Inadequate knowledge of French is a contributing factor to the higher unemployment rates experienced by young English- speakers. A lack of work, and a hampered ability to take part in public life in general, lead to the disenfranchisement of members of this community. Given the high demand among young English- speakers for more French-language training, policy makers must come up with new and creative ways of meeting the demand.

Report of the Priority Setting Steering Committee Related to the 2018 Community Consultation - Quebec Community Groups Network (QCGN) (2018)
In March 2018, the Government of Canada renewed its official languages strategy, called the Action Plan for Official Languages 2018-2023: Investing in Our Future. Amongst other investments contained in the Action Plan, the Department of Canadian Heritage (PCH), was provided resources to increase the amount of funds available to the community sector through the Cooperation with the Community Sector – Development of Official Language Communities program, and, a development fund was established specifically for English-speaking Quebec.
Keywords: Official Language Minority Community (OLMC)

Community-based Process Results in Strong Watchdog Committee for English Health and Social Services - Quebec Community Groups Network (QCGN) (2018)

QCGN Advocates a More Community-driven Process for Provincial Funding - Quebec Community Groups Network (QCGN) (2018)

Cabinet Shuffle Blurs Roles and Could Delay Implementation of Action Plan for Official Languages - Quebec Community Groups Network (QCGN) (2018)
Keywords: Official Language Minority Community (OLMC)

VEQ's Summer 2018 Newsletter - Voice of English-speaking Quebec (VEQ) (2018)

Brief by the Consortium of Official Language Minority Community Media, Presented to the Standing Senate Committee on Official Languages Within the Context of its Study on Canadians' Views About Modernizing the Official Languages Act - Sonier, Francis; Demers, Paul; Bonspiel, Steve (2018)
The Consortium of Official Language Minority Community Media (the Consortium) is an alliance of the three national organizations representing official language minority community media in Canada: the Association de la presse francophone (APF), the Alliance des radios communautaires du Canada (ARC du Canada) and the Quebec Community Newspapers Association (QCNA). Since 2016, the Consortium has been the common voice of all three of its members on a number of issues.
Keywords: Official Language Minority Community (OLMC)

QCGN Set To Champion English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2018)
Keywords: Official Language Minority Community (OLMC)

Action Plan for Official Languages 2018-2023 Highlights (2018)

Bonjour Hi : What French and English Quebecers Think About Each Other and About Key Issues - Jedwab, Jack; Warren, Jean-Philippe (2018)

Network News - Quebec Community Groups Network (QCGN) (2018)

QCGN Applauds Priorities in Commissioner's Annual Report - Quebec Community Groups Network (QCGN) (2018)

English-speaking Quebec and the Modernization of the Official Languages Act : Brief Submitted to the Standing Senate Committee on Official Languages Study on Canadians' Views about Modernizing the Official Language Act - Sandilands, Marion (Quebec Community Groups Network (QCGN), 2018)
The Quebec Community Groups Network (“QCGN”) welcomes this opportunity to contribute to this Committee’s study on modernizing the Official Languages Act (“the Act”). In the spirit of modernization, the QCGN takes this opportunity to present a picture of the contemporary English-speaking community of Quebec. As this Committee noted in 2011, there are certain widely-held myths regarding this community. The QCGN hopes to contribute to a modernized understanding of this community and its role as a unique and important official language minority community in Canada.
Keywords: Official Language Minority Community (OLMC)

Guide to the Development of Access Programs for Health and Social Services in the English Language - Kosseim, Mylène; Prata, Ghislaine (Community Health and Social Services Network (CHSSN), 2018)
This Guide provides institutions with a common provincial framework It describes the steps institutions must follow to develop their access program for health and social services in the English language (hereafter “access program”). It takes three key principles into consideration: the relationship between effective communication and successful clinical interventions; the needs expressed by the English-speaking community with respect to access to health and social services in their language; the assessment of results in a context of continuous improvement.

QCGN/Community Pleased with Funding from Secretariat - Quebec Community Groups Network (QCGN) (2018)

Long Awaited Regulation Creating Provincial Access to Committee a First Step in the Right Direction - Quebec Community Groups Network (QCGN) (2018)

Recommendations from the Youth Unemployment Forum Held on December 5, 2017 - Youth Employment Services (YES) (2018)
In Quebec and indeed across Canada we are confronting the many and varied challenges of a rapidly evolving labour market. New technologies are developing at a rate that is challenging our institutions; globalization is bringing increasing unpredictability to economic systems; traditional management models are being disrupted by the growing sharing and gig economies. Youth may have adapted quickly to high-tech society, however it would be disastrous to assume they will adjust as easily to the trials of the Fourth Industrial Revolution. Today’s youth need innovative supports to help them to survive in and capitalize on the complexities of the future economy. While Québec youth have never been more highly educated or bilingual, young job seekers andemployers alike are frustrated. Not enough has been done to curb the outmigration of educated youth nor to create an equitable environment for underrepresented populations. It hardly matters that jobs may be available, if youth are not here or not able to connect with them. This is why, with support from Canadian Heritage, on December 5th, 2017 YES convened a daylong forum bringing together multiple sectors from throughout the province of Quebec, to develop a deeper understanding of the unique employment barriers faced by Quebec’s Official Language Minority Community (OLMC) youth.
Keywords: Official Language Minority Community (OLMC)

QCGN Welcomes New Federal Investments in English-speaking Quebec - Quebec Community Groups Network (QCGN) (2018)
Keywords: Official Language Minority Community (OLMC)

QCGN Welcomes New Budget Measures for English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2018)

Demographic Profile of the English-speaking Communities : Administrative Region of Montréal & the Rest of Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Abitibi-Témiscamingue & MRC Abitibi - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Abitibi-Témiscamingue & MRC La Vallée-de-l'Or - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Abitibi-Témiscamingue & MRC Rouyn-Noranda - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Abitibi-Témiscamingue & MRC Témiscamingue - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Bas-Saint-Laurent & MRC Rimouski-Neigette - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Capitale-Nationale & MRC La Côte-de-Beaupré - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Capitale-Nationale & MRC La Jacques-Cartier - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Capitale-Nationale & MRC Portneuf - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Capitale-Nationale & MRC Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Centre-du-Québec & MRC Arthabaska - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Centre-du-Québec & MRC Drummond - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Chaudière-Appalaches & MRC Beauce-Sartigan - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Chaudière-Appalaches & MRC Bellechasse - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Chaudière-Appalaches & MRC Les Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Chaudière-Appalaches & MRC Lévis - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Côte-Nord & MRC Caniapiscau - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Côte-Nord & MRC Le Golfe-du-Saint-Laurent - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Côte-Nord & MRC Manicouagan - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Côte-Nord & MRC Sept-Riviéres - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Estrie & MRC Coaticook - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Estrie & MRC Le Granit - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Estrie & MRC Le Haut-Saint-François - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Estrie & MRC Le Val-Saint-François - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Estrie & MRC Les Sources - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Estrie & MRC Memphrémagog - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Estrie & MRC Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Gaspésie-Îles-de-la-Madeleine & MRC Avignon - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Gaspésie-Îles-de-la-Madeleine & MRC La Côte-de-Gaspé - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Gaspésie-Îles-de-la-Madeleine & MRC Le Rocher-Percé - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Gaspésie-Îles-de-la-Madeleine & MRC Les Îles-de-la-Madeleine - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Lanaudière & MRC D'Autray - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Lanaudière & MRC Joliette - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Lanaudière & MRC L'Assomption - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Lanaudière & MRC Les Moulins - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Lanaudière & MRC Matawinie - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Lanaudière & MRC Montcalm - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laurentides & MRC Antoine-Labelle - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laurentides & MRC Argenteuil - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laurentides & MRC Deux-Montagnes - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laurentides & MRC La Rivière-du-Nord - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laurentides & MRC Les Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laurentides & MRC Les Pays-d'en-Haut - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laurentides & MRC Mirabel - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laurentides & MRC Thérèse-de Blainville - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Laval & the Rest of Quebec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Mauricie & MRC La Tuque - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Mauricie & MRC Maskinongé - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Mauricie & MRC Shawinigan - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Mauricie & MRC Trois-Riviéres - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of The English Speaking Communities in the Administrative Region of Montérégie & MRC Beauharnois-Salaberry - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Montérégie & MRC Brome-Missisquoi - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Montérégie & MRC La Haute-Yamaska - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.
Keywords: Official Language Minority Community (OLMC)

Demographic Profile of The English Speaking Communities in the Administrative Region of Montérégie & MRC La Vallee-du-Richelieu - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of The English Speaking Communities in the Administrative Region of Montérégie & MRC Le Haut-Richelieu - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of The English Speaking Communities in the Administrative Region of Montérégie & MRC Le Haut-Saint-Laurent - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of The English Speaking Communities in the Administrative Region of Montérégie & MRC Les Jardins de Napierville - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of The English Speaking Communities in the Administrative Region of Montérégie & MRC Les Maskoutains - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of The English Speaking Communities in the Administrative Region of Montérégie & MRC Marguerite-d'Youville - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Montérégie & MRC Pierre-de Saurel - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.
Keywords: Official Language Minority Community (OLMC)

Demographic Profile of The English Speaking Communities in the Administrative Region of Montérégie & MRC Roussillon - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of The English Speaking Communities in the Administrative Region of Montérégie & MRC Rouville - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of The English Speaking Communities in the Administrative Region of Montérégie & MRC Vaudreuil-Soulanges - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Outaouais & MRC Gatineau - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Outaouais & MRC La Vallee-de-la-Gatineau - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Outaouais & MRC Les Collines-de-l'Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Outaouais & MRC Papineau - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Outaouais & MRC Pontiac - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Saguenay-Lac-Saint-Jean & MRC Saguenay - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Network News - Quebec Community Groups Network (QCGN) (2018)

VEQ's Spring 2018 Newsletter - Voice of English-speaking Quebec (VEQ) (2018)

QCGN Welcomes Promises of New Investments in Official Languages - Quebec Community Groups Network (QCGN) (2018)

CAQ Misses the Mark with Scheme to Abolish School Boards - Quebec Community Groups Network (QCGN) (2018)

Chit Chat Club : Improve Your Second Language Skills While Lending a Helping Hand - Centre Wellness (2018)

Adaption Gaspésie-Les-Îles 2014-2018 : Improved Access to Inter-Regional Health and Social Services for the English-speaking Population of Gaspésie-Îles-de-la-Madeleine - Community Health and Social Services Network (CHSSN) (2018)

Annual Report 2017-2018 - Community Health and Social Services Network (CHSSN) (2018)
Keywords: Official Language Minority Community (OLMC)

Building Confidence : Conversing with the English Community : A How-to Toolkit - Community Health and Social Services Network (CHSSN) (2018)

CHSSN Community Netlink - Community Health and Social Services Network (CHSSN) (2018)

Main Achievements 2014-2018 - Dialogue McGill (2018)

Key Demographic and Socio-Economic Characteristics of Quebec's English-speaking Youth (25-29) - JPocock Research Consulting (Community Health and Social Services Network (CHSSN), 2018)
This CHSSN report profiles the situation of English-speaking citizens of Quebec who are engaged in the numerous transitions that are typically encountered between the ages of 15 and 29 in the critical passage from childhood to adulthood.

Demographic Profiles of English-speaking Communities : RLS de la Baie des Chaleurs (1111) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RLS de la Cote de Gaspe (1113) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RLS du Rocher Perce (1114) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Abitibi-Témiscamingue & RLS de l'Abitibi (0812) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Gaspesie (1110) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Centre & RLS de Champlain (1611) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Participation of English-speaking Canadians in the Federal Civil Service in Quebec (outside of the National Capital Region) - Quebec Community Groups Network (QCGN) (2018)

Changes to Article II Constitution : Resolution 2018-03 - Quebec Federation of Home and School Associations (QFHSA) (2018)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2018)

Resolution 2018-02 : Wider Access to English Education - Quebec Federation of Home and School Associations (QFHSA) (2018)
Keywords: Official Language Minority Community (OLMC)

Annual Report : 2017-2018 - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)

Health and Social Service Resources for English-Speaking Communities in the East and North of Montreal : 2018 - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)

Health and Social Service Resources for the English-speaking Seniors in the East end of Montreal - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)

Reisaction Newsletter - Réseau de l’est de l’île pour les services en anglais (REISA) (2018)

Annual Report 2017-18 - The English Speaking Catholic Council (ESCC) (2018)

Annual Report 2017-2018 - Voice of English-speaking Quebec (VEQ) (2018)

Improving the Spectrum of Services Offered to English-Speaking Seniors : CIUSSS de la Capitale-Nationale’s Experience Implementation Project: 2014-2018 - Paquette, Brigitte (2017)

News from the Evidence Base : Findings from the 2016 Census of Canada - Pocock, Joanne (2017)
Keywords: Official Language Minority Community (OLMC)

Provision of Services by English-Speaking Agent - Vienney, Annie; Dufour, Claudiane; Sullivan, Sharleen (2017)

Community Leaders Ready to Assist Kathleen Weil, Quebec's New Minister Responsible for Relations with English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2017)

Report on the Health and Social Services Priorities of English-speaking Communities in Quebec - Carter, James; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
In July 2017, the CHSSN submitted the present report to the Quebec Ministry of Health and Social Services inviting it to undertake consultations with key public institutions and community representatives with respect to the recommendations. The objective was to ensure that a proposal to Health Canada reflected the shared commitment of Quebec and its English-speaking communities to work in partnership to improve access to health and social services in English. In its reply to the CHSSN in October 2017 (Appendix), the Ministry supported the recommendations in accordance with comments reflecting the results of its consultations with the public institutions. To support Health Canada in its mandate to prepare a new Contribution Program, the sponsoring organizations of the twenty recognized community health and social services networks along with the CHSSN are submitting the present report and recommendations reflecting the continuity of results of the last federal contribution and emergence of new priorities for the period ahead.
Keywords: Official Language Minority Community (OLMC)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2017)

QCGN Welcomes Nomination of Kathleen Weil as Minister Responsible for Relations with English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2017)

Language Training Program : Report on interviews with health and social services network respondents - Farley, Roger (Dialogue McGill, 2017)

A Website Created to Support English-speaking Patients from Eastern Regions in Quebec Traveling Away from Home for Medical Services - Community Health and Social Services Network (CHSSN) (2017)

Community Looks Forward to MUHC Resolution - Quebec Community Groups Network (QCGN) (2017)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2017)

Composite Indicators for Community Vitality - Estrie (QC) - Floch, William; Abou-Rjeili, Elias; Durand, Martin (2017)
Keywords: Official Language Minority Community (OLMC)

QCGN Welcomes Creation of New Secretariat in Premier's Office - Quebec Community Groups Network (QCGN) (2017)

QCGN Looks Forward to Champion for All Official Language Minority Communities - Quebec Community Groups Network (QCGN) (2017)
Keywords: Official Language Minority Community (OLMC)

QCGN Pledges Constructive, Positive Role in Process Launched Today by Premier - Quebec Community Groups Network (QCGN) (2017)

QCGN Invites Meilleur to Become Acquainted with English-speaking Quebec - Quebec Community Groups Network (QCGN) (2017)
Keywords: Official Language Minority Community (OLMC)

QCGN Shares Concerns Over Selection Process for Commissioner of Official Languages - Quebec Community Groups Network (QCGN) (2017)
Keywords: Official Language Minority Community (OLMC)

Let's Shift the Focus to Underlying Issues at McGill University Health Centre - Quebec Community Groups Network (QCGN) (2017)

Presentation by Youth Employment Services (YES) to the Standing Senate Committee on Official Languages and the English-speaking Community in Quebec - Youth Employment Services (YES) (2017)
YES (Youth Employment Services) is a non-for-profit charity whose mission is to enrich the community by providing English-language services to help people find jobs and start small and medium size businesses.
Keywords: Official Language Minority Community (OLMC)

Annex - List of Funded Projects - Quebec Community Groups Network (QCGN) (2017)

Social Initiatives to Address Needs of Vulnerable English-speaking Youth, Seniors and Newcomers - Quebec Community Groups Network (QCGN) (2017)

Tradition Allows MNA Coiteux to Speak English in National Assembly - Quebec Community Groups Network (QCGN) (2017)

French Language Study Program : Immigration and Education Officials Need to Find Solution, Not Cast Aspersions on Students and English School Boards - Quebec Community Groups Network (QCGN) (2017)

Quebec Community Groups Network Brief to House of Commons Standing Committee on Official Languages : Full Implementation of the Official Languages Act in the Canadian Justice System - Quebec Community Groups Network (QCGN) (2017)
The Quebec Community Groups Network (QCGN) is pleased to submit the following brief to the House of Commons Standing Committee on Official Languages’ (LANG) study on the Full Implementation of the Official Languages Act in the Canadian Justice System. We understand the Committee’s objective is to examine how and to what extent the Official Languages Act is applied in areas of justice that fall under federal jurisdiction. The Committee should know that English-speaking Quebec does not yet possess the level of capacity in this sector represented by organizations like the Fédération des associations de juristes d'expression française de common law, the Centre canadien de français juridique, or the Réseau national de formation en justice. We do not have researched and coherent policy proposals, nor even a developed Quebec-wide network of English-speaking jurists. We are hopeful however that this capacity will develop, and the QCGN continues to actively support the newly formed Association of English-speaking Jurists of Quebec (AESJQ), who have submitted their own brief towards this study.
Keywords: Official Language Minority Community (OLMC)

Presentation to the Committee on Culture and Education on Bill 86 - Duszara, Walter; Chambers, Geoffrey; Maldoff, Eric; Martin-Laforge, Sylvia (2017)

QCGN Hopeful About Opportunities for Official Language Minority Communities in Federal Budget - Quebec Community Groups Network (QCGN) (2017)
Keywords: Official Language Minority Community (OLMC)

QCGN to Host Conference on Community Engagement and the Integration of Newcomers - Quebec Community Groups Network (QCGN) (2017)

Bilingual Young Quebecers Leading the Way to Canada's Future - Quebec Community Groups Network (QCGN) (2017)

A Needs Assessment : Better Understanding the Current Situation of the Senior Population - Burke, Helena; Craig, Lisa; Richardson, Mary (Council for Magdalen Islanders (CAMI), 2017)
This needs assessment was conducted as part of a community development process in the English-speaking community of Grosse-Ile, on the Magdalen Islands, Quebec. It is part of the follow- up to a community portrait that was developed through a participatory process in early 2015. The process involved the mobilization and engagement of a number of local stakeholders as well as community residents who expressed their views on a number of different themes. One of the issues that was highlighted by community members as a concern, even a priority, was that of the aging population within the ESC, having access to few services and limited support for caregivers.
Keywords: Official Language Minority Community (OLMC)

Supporting English-speaking Children and Families in the Gaspé and Magdalen Islands 2017-2020 - Community Health and Social Services Network (CHSSN); Council for Anglophone Magdalen Islanders (CAMI); Vision Gaspé-Percé Now; Committee for Anglophone Social Action (CASA) (2017)
The official language minority community of this region has the poorest socioeconomic status in Canada when aspects such as low education levels, unemployment and low income tendencies are analyzed. Children are particularly affected by this status. Children ages 0 to 5 make up 6.6% of the total English-speaking population.
Keywords: Official Language Minority Community (OLMC)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2017)

The Network Model : Influencing Public Policy for Social Change - Community Health and Social Services Network (CHSSN) (2017)
The case studies being presented in today demonstrate that the development principles are at work every day and are now being pressed into new areas of action. The values underpinning the network model include promoting the identity of our communities, promoting social inclusion and advocating for equity in the broader society in its treatment of communities. These values can support network strategies to enter the “next level” of participation in societal initiatives setting broad policy goals. The reward for such effort can be societal recognition that the programs that define Quebec’s commitment to social progress also include our communities.

QCGN Welcomes Resurrection of Independent Court Challenges Program - Quebec Community Groups Network (QCGN) (2017)

Health Passport : When Language Matters / Passport santé : Question de langue - Assistance and Referral Centre (ARC) (2017)

Active Offer : A Culture of Respect, a Culture of Excellence - Canada. Office of the Commissioner of Official Languages (2017)

Building Together : Succesful Partnerships Between Community and the Health and Social Services System - Community Health and Social Services Network (CHSSN) (2017)
The Community Health and Social Services Network (CHSSN) coordinates a Quebec-wide health and social services “Adaptation Program” designed to enhance the vitality of English-speaking minority communities in Quebec by increasing access to existing health and social services for Englishspeaking Quebecers. The program is supported by an investment from Health Canada and has been undertaken in partnership with the ministère de la Santé et des Services sociaux (MSSS). An implementation agreement between CHSSN and the MSSS was concluded to incorporate the projects into Quebec’s initiatives to improve access to health and social services in English through partnerships between local English-speaking communities and health and social services system.
Keywords: Official Language Minority Community (OLMC)

Community NetLink - Community Health and Social Services Network (CHSSN) (2017)

Community NetLink - Community Health and Social Services Network (CHSSN) (2017)

2016-2017 Funded Projects - Dialogue McGill (2017)

Dialogue : Better Communication for Better Care - Dialogue McGill (2017)

Dialogue : Better Communication for Better Care - Dialogue McGill (2017)

Demographic Profiles of English-speaking Communities in RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities in RTS de l'Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities in RTS du Centre-Sud-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities in RTS du Nord-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Chaudière-Appalaches (1210) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Chaudière-Appalaches & RLS Alphonse-Desjardins (1211) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Chaudière-Appalaches & RLS de Beauce (1213) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Chaudière-Appalaches & RLS de la région de Thetford (1212) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Abitibi-Témiscamingue & RLS de Rouyn-Noranda (0813) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Abitibi-Témiscamingue & RLS du Témiscaming (0815) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Abitibi-Témiscamingue & RLS Vallée-de-l'Or (0814) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Est-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Est-de-l'Île-de-Montréal & RLS de Hochelaga - Mercier-Ouest - Rosemont (0653) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Est-de-l'Île-de-Montréal & RLS de Rivière-des-Prairies - Anjou - Montréal-Est (0652) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Est-de-l'Île-de-Montréal & RLS de Saint-Léonard - Saint-Michel (0651) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke & RLS d'Asbestos (0517) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke & RLS de Coaticook (0514) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke & RLS de la Haute-Yamaska (0512) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke & RLS de la Pommeraie (0511) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke & RLS de Sherbrooke (0514) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke & RLS de Val Saint-François (0516) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke & RLS du Granit (0519) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie - CHU de Sherbrooke & RLS du Haut-Saint-François (0518) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Estrie & RLS de Memphrémagog (0513) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Ouest-de-l'Île-de-Montréal & RLS de Dorval - Lachine - Lasalle (0612) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Ouest-de-l'Île-de-Montréal & RLS de Pierrefonds - Lac Saint-Louis (0611) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Outaouais & RLS de Grande-Rivière - Hull - Gatineau (0714) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Outaouais & RLS de la Vallée-de-la-Gatineau (0712) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Outaouais & RLS de la Vallée-de-la-Lièvre et de la Petite-Nation (0715) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Outaouais & RLS des Collines-de-l'Outaouais (0713) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de l'Outaouais & RLS du Pontiac (0711) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Capitale-Nationale & RLS de Portneuf (0311) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Capitale-Nationale & RLS de Québec-Sud (0312) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Capitale-Nationale & RLS Québec-Nord (0313) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Côte-Nord - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Côte-Nord & RLS de Kawawachikamach (0917) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Côte-Nord & RLS de la Basse-Côte-Nord (0916) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Côte-Nord & RLS de la Haute-Côte-Nord - Manicouagan (0912) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Côte-Nord & RLS de Sept-Îles (0914) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS d'Arthabaska-de l'Érable (0418) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS de Bécancour - Nicolet-Yamaska (0416) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS de Drummond (0417) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS de Trois-Rivières (0415) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS du Centre-de-la-Mauricie (0414) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS du Haut-Saint-Maurice (0411) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Centre (1610) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Centre & RLS du Haut-Richelieu - Rouville (1612) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Est (1620) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Est & RLS de Richelieu-Yamaska (1622) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Est & RLS Pierre-Boucher (1621) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Est & RLS Pierre-de Saurel (1623) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Ouest (1630) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Ouest & RLS de Jardins-Roussillon (1634) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Ouest & RLS de Vaudreuil-Soulanges (1631) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Ouest & RLS du Haut-Saint-Laurent (1633) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Montérégie-Ouest & RLS du Suroît - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Lanaudière (1410) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Lanaudière & RLS de Lanaudière-Nord (1411) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Lanaudière & RLS de Lanaudière-Sud (1412) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de Laval (1310) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides (1510) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS d'Antoine-Labelle (1511) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS d'Argenteuil (1514) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS de Deux-Montagnes - Mirabel-Sud (1515) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS de La Rivière-du-Nord - Mirabel-Nord (1516) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS de Thérèse-de Blainville (1517) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS des Laurentides (1512) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS des Laurentides & RLS des Pays-d'en-Haut (1513) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Bas-Saint-Laurent - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Bas-Saint-Laurent & RLS de Rimouski (0115) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Centre-Ouest-de-l'Île-de-Montréal & RLS de Côte-des-Neiges - Métro - Parc-Extension (0622) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Centre-Ouest-de-l'Île-de-Montréal & RLS de Côte-Saint-Luc - NDG - Montréal-Ouest (0621) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Centre-Sud-de-l'Île-de-Montréal & RLS de Verdun - Côte St-Paul - St-Henri - Pointe-St-Charles (0631) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Centre-Sud-de-l'Île-de-Montréal & RLS des Faubourgs - Plateau-Mont-Royal - St-Louis-du-Parc (0632) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Nord-de-l'Île-de-Montréal & RLS d'Ahuntsic - Montréal-Nord (0642) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Nord-de-l'Île-de-Montréal & RLS de la Petite Patrie - Villeray (0643) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Nord-de-l'Île-de-Montréal & RLS du Nord de l'Île - Saint-Laurent (0641) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Saguenay-Lac-Saint-Jean - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Saguenay-Lac-Saint-Jean & RLS de Chicoutimi (0215) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Saguenay-Lac-Saint-Jean & RLS de Jonquière (0214) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS du Saguenay-Lac-Saint-Jean & RLS de La Baie (0216) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Annual Report : 2016-2017 - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)

Health and Social Service Resources for English-Speaking Communities in the East and North of Montreal : 2017 - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)

Health and Social Service Resources for the English-speaking Seniors in the East end of Montreal - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)

Annual Report - Vision Gaspé-Percé Now (VGPN) (2017)

Annual Report - Vision Gaspé-Percé Now (VGPN) (2017)

Annual Report 2016-2017 - Voice of English-speaking Quebec (VEQ) (2017)

English-speaking Quebec Must Have a Stronger Voice in Conversation About Official Languages - Quebec Community Groups Network (QCGN) (2016)
Keywords: Official Language Minority Community (OLMC)

Network News - Quebec Community Groups Network (QCGN) (2016)

Access to Justice for Minority Populations : Focus on the English-speaking Communities of Quebec: 2000-2016 - Shohet, Linda (Quebec Community Groups Network (QCGN), 2016)
The objectives of this project are to research access to justice issues experienced by English-speaking Quebecers from their perspective, to establish metrics for measuring access to justice that fit the needs of community members, and to make recommendations to mitigate or overcome gaps and challenges for the English-speaking community of Quebec. The guiding question is: What is the lived experience for an English-speaking Quebecer in accessing legal and judicial information and services or in interacting with any of the social services that are now understood to be implicated in the broader concept of access to justice? This literature review is the first deliverable from Phase 1 of the project with an expectation that the findings will inform the second deliverable — a research plan to fill gaps in knowledge about the reality of access to justice for the anglophone population of Quebec.

Public Consultation on Canadian Content in a Digital World - English Language Arts Network (ELAN); Forget, Bettina; Rodgers, Guy (2016)
Keywords: Official Language Minority Community (OLMC)

QCGN Advocates for More Flexible Regulations for Provision of Federal Minority Language Services - Quebec Community Groups Network (QCGN) (2016)
Keywords: Official Language Minority Community (OLMC)

Community Innovation Fund Seeking Proposals to Better Serve Vulnerable Youth, Seniors/Caregivers or Newcomers in Quebec's English-language Communities - Quebec Community Groups Network (QCGN) (2016)
Keywords: Official Language Minority Community (OLMC)

QCGN Discusses Concerns of English-speaking Community with Premier Couillard - Quebec Community Groups Network (QCGN) (2016)

QCGN Appearance before the House of Commons Standing Committee on Official Languages - Quebec Community Groups Network (QCGN) (2016)

Demographic Summaries for English-speaking Populations Across Quebec's RTS Territories (2011) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
This document contains a series of one-page summaries highlighting the key demographic characteristics of the English-speaking populations for each of the new health territories established by the MSSS in 2015 as part of the re-organization of health services. The 25 health geographies in this series are the RTS which is the French-language acronym for the Réseau territoriale des services which correspond to the CISSS and CIUSSS territories. This series is intended as a knowledge resource for the CHSSN NPI networks.

Network News - Quebec Community Groups Network (QCGN) (2016)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2016)

Short History of Official Language Advocacy : English-Language Television in Quebec - English Language Arts Network (ELAN) (2016)
Keywords: Official Language Minority Community (OLMC)

Educational Institutions Must Tie Their Activities to the Vitality of the Communities They Serve - Quebec Community Groups Network (QCGN) (2016)

Brief to the Committee on Culture and Education : Special Consultations and Public Hearings on Bill 105, An Act to Amend the Education Act - Quebec Community Groups Network (QCGN) (2016)
The Quebec Community Groups Network (QCGN) represents forty-eight (48) English-language community groups across Quebec. QCGN recognizes that Quebec’s English public school system is a key institution of the English-speaking community of Quebec - a linguistic minority community. The management and control of these institutions is a matter of governance subject to minority language educational rights contained in the Canadian Charter of Rights and Freedoms, and Quebec’s democratic tradition, expressed in the political rights guaranteed by the Quebec Charter of Human Rights and Freedoms.
Keywords: Official Language Minority Community (OLMC)

Network News - Quebec Community Groups Network (QCGN) (2016)

Statement from the Quebec Community Groups Network Following the Passing of Mauril Bélanger - Quebec Community Groups Network (QCGN) (2016)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2016)

Towards Renewing the Strategic Priorities of the English-speaking Community of Quebec - Quebec Community Groups Network (QCGN) (2016)

QCGN Welcomes Canadian Heritage Minister and Bids Adieu to President and Commissioner - Quebec Community Groups Network (QCGN) (2016)

Keeping the Door Open for Young English-speaking Adults in Québec : Language Learning in English Schools and Centres - Advisory Board on English Education (2016)
During a committee hearing in April 2015, Premier Philippe Couillard responded to a question from Mr. David Birnbaum (MNA for D’Arcy-McGee) about “what our government has done and plans to do to ensure that young anglophone Quebecers are full and valued participants in building our future,” by saying that he wanted to hear from the English-speaking community. About the same time, then-Minister of Education Bolduc asked the Advisory Board on English Education (ABEE) to advise him on how to encourage English-speaking youth to remain in Québec. In May 2016, Premier Couillard identified the English educational sector as a model for the system as a whole, and the Board proposed some reasons for this success in its most recent brief. It should be noted that students in the English sector achieve this success while receiving instruction in two languages from kindergarten onward. The ability to function in two languages is recognized as a crucial socio-economic skill for young Anglophones, and has an impact on their decision whether or not to stay in Québec. How can the education system contribute to developing this skill? This brief is respectfully presented to the Minister of Education with recommendations that respond to this question.

In Touch - Jeffery Hale - Saint Brigid's (JHSB) (2016)

A New Multi-year Official Languages Plan to Support Canada’s English Linguistic Minority Communities - Quebec Community Groups Network (QCGN) (2016)
This aim of this document is to outline the strategic priorities of the English-speaking Community of Quebec (ESCQ), and its high-level expectations from a new multi-year Official Languages Plan to support Canada’s English linguistic minority communities. Sector and regional leaders have developed their own priorities and expectations, which the strategic priorities contained hereunder support.
Keywords: Official Language Minority Community (OLMC)

Network News - Quebec Community Groups Network (QCGN) (2016)

QCGN Praises Commissioner Fraser for a Decade of Support to Quebec's English-speaking Community - Quebec Community Groups Network (QCGN) (2016)

English-speaking Quebecers to Benefit from Investment Fund for Official Language Minority Communities - Quebec Community Groups Network (QCGN) (2016)
Keywords: Official Language Minority Community (OLMC)

Digital Steps Offer Renewed Vitality for Media Serving Quebec's English-speaking Minority - Quebec Community Groups Network (QCGN) (2016)

Language Minorities Need Separate Rights Support Program - Quebec Community Groups Network (QCGN) (2016)

2015 CHSSN-CROP Survey on Community Vitality : Findings on English-speaking Community Vitality Across Key Sectors - Pocock, Joanne (Community Health and Social Services Network, 2016)
This 2015-2016 Baseline Data Report relays key findings of the 2015 CHSSN/CROP Survey on Community Vitality as they unfold across key sectors. The commonalities and distinct features of regional communities within the English-speaking provincial population are delineated as well as sub-groups defined by gender, age, household income and level of bilingualism. This report from the 2015 survey is intended as a companion to the 2015-2016 Baseline Data Report entitled English Language Access to Health and Social Services in Québec, which includes a summary of results from Focus Group sessions conducted in several regions around the province.

Baseline Data Report 2015-2016 : English-language Health and Social Services Access in Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
This 2015-2016 Baseline Data Report relays the health and social service findings of the 2015 CHSSN/CROP Survey on Community Vitality. The commonalities and distinct features of regional communities within the English-speaking provincial population are delineated as well as sub-groups defined by gender, age, household income, health status and level of bilingualism. While this report is limited to the health and social service sector, the Survey on Community Vitality (2005, 2010, and 2015) also collects the opinions, perceptions and expectations of a representative sample of English-speaking Quebecers in most regions of Quebec with respect to issues in education, human resource development, justice, culture and communications. The 2015 study replicates previous surveys conducted by CROP in 2000 for the Missisquoi Institute and again in 2005 and 2010 for the CHSSN.
Keywords: Official Language Minority Community (OLMC)

Report : Community Network Forum - Community Health and Social Services Network (CHSSN) (2016)
Health promotion is an activity that community organizations can adopt to enhance visibility and credibility in their communities. Health promotion activities can respond to real needs of different groups and create opportunities to engage the public system with the community organization and the constituencies it serves. For the public network, a community organization that has established a health promotion role has the potential to become a prime partner in helping an institution better serve its target population. In recent years, community networks have developed health promotion programs that have reached thousands of community members and can now demonstrate positive results. The Forum will discuss how this development is resulting in promising and best practices, and inspiring a range of public and community interests to engage in health promotion for English-speaking communities.

Building Community Capacity From Evidence to Action (2015-2016) - Pocock, Joanne (2016)

Quebec Youth to Discuss Their Place in Canada at Second Annual Youth Forum - Quebec Community Groups Network (QCGN) (2016)

English-language Interpretation Services to Improve Language Access to Health and Social Services for Members of English-speaking Communities in Quebec : Status Report - Kosseim, Myléne (Community Health and Social Services Network (CHSSN), 2016)
This study aims to document the current situation regarding the use of formal interpreters as a means of language access to health and social services for English-speaking persons and to propose possible improvements to the Ministère de la Santé et des Services sociaux.
Keywords: Official Language Minority Community (OLMC)

A Brief on Bill 86 : An Act to Modify the Organization and Governance of School Boards to Give Schools a Greater Say in Decision-making and Ensure Parents' Presence Within Each School Board's Decision-making Body - Quebec Federation of Home and School Associations (QFHSA) (2016)
To say that the English‐speaking community dislikes the proposed Bill 86 would be a gross understatement. To say the English‐speaking community views Bill 86 as an attack on its continued existence in Quebec is the more accurate view of the community’s feelings about this “projet de loi”. The community senses, with this bill, a fundamental shift that seeks to completely submerge and eradicate any public sign of the presence of the English‐speaking community in Quebec. The community feels threatened not only about the future of its schools, but equally about its continued existence as an entity. The impression is that the present government is pursuing a systematic dismantling of the public institutions serving the English‐speaking community and increasingly diminishing its role in the public life of the province. The importance of the presence of our public institutions cannot be understated either, as they are an extremely important social construct acting as central pillars or anchors on which our community is built. The dictionary defines an institution as follows: “an organization, establishment, foundation, society, or the like, devoted to the promotion of a particular cause or program, especially one of a public, educational, or charitable character.”
Keywords: Official Language Minority Community (OLMC)

Portrait of the English-speaking Community of Richmond - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2016)
This portrait has been completed by Townshippers’ Association and the Community Health and Social Services Network (CHSSN), in collaboration with the Centre de santé et des services sociaux Val-Saint-François and the Richmond & Region Community Learning Center. Townshippers’ Association is a non-profit, non-partisan community organization focused on promoting and supporting the interests of the English-speaking minority community in the Eastern Townships region of Quebec. The Association was founded in 1979 to ensure the English-speaking community would remain visible despite a declining population. Through a variety of initiatives, Townshippers’ works to strengthen the community and culture of English-speaking Townshippers, open doors of opportunity for youth and promote access to health, social and other services in English. Townshippers’ also strives to encourage the active participation of English-speakers in all aspects of the greater community, in order to help the English-speaking community of the Eastern Townships build bridges with their French-speaking neighbours. The main objective of this portrait is to contribute to a more in-depth understanding of the English-speaking community of Richmond and the surrounding area, in order to inform future actions.
Keywords: Official Language Minority Community (OLMC)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2016)

Brief to the Committee on Culture and Education : Quebec and the Minority Language Educational Rights and Canada’s English Linguistic Minority Communities: A New Partnership - Quebec Community Groups Network (QCGN) (2016)
Voting in elections is an intrinsic right for all Quebecers. It is beyond democratic tradition for government to capriciously remove these rights without a pressing and substantial reason. Quebec’s English public school system is a key institution of the English-speaking community of Quebec, a linguistic minority community. The management and control of these institutions is a matter of governance subject to minority language educational rights contained in the Canadian Charter of Rights and Freedoms, and Quebec’s democratic tradition, expressed in the political rights guaranteed by the Quebec Charter of Human Rights and Freedoms.
Keywords: Official Language Minority Community (OLMC)

QCGN Demands Apology from Prime Minister Trudeau - Quebec Community Groups Network (QCGN) (2016)
Keywords: Official Language Minority Community (OLMC)

Key Socio-demographic Characteristics of English-speaking Children, 2011 Gaspésie – Îles-de-la-Madeleine and Census Divisions - Pocock, Joanne (2016)

Black in Quebec : Part 1 - Black Community Resource Centre (BCRC) (2016)

Our Region - Centre for Access to Services in English (CASE) (2016)

Children 0 to 5 and their Parents : RTS de Chaudière-Appalaches - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de l'Abitibi-Témiscamingue - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de l'Est-de-l'Île-de-Montréal - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de l'Estrie – CHU de Sherbrooke - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de l'Ouest-de-l'Île-de-Montréal - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de l'Outaouais - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de la Capitale-Nationale - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de la Côte-Nord - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de la Gaspésie - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de la Mauricie-et-du-Centre-du-Québec - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de la Montérégie-Centre - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de la Montérégie-Est - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de la Montérégie-Ouest - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de Lanaudière - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS de Laval - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS des Îles - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS des Laurentides - Community Health and Social Services Network (CHSSN) (2016)

Children 0 to 5 and their Parents : RTS des Terres-Cries-de-la-Baie-James - Community Health and Social Services Network (CHSSN) (2016)

Community NetLink - Community Health and Social Services Network (CHSSN) (2016)

Community NetLink - Community Health and Social Services Network (CHSSN) (2016)

2015-2016 Funded Projects - Dialogue McGill (2016)

Dialogue : Better Communication for Better Care - Dialogue McGill (2016)

Dialogue : Mieux communiquer pour mieux soigner - Dialogue McGill (2016)

Brief for Official Language Policy Review 2016 - English Language Arts Network (ELAN) (2016)
ELAN was conceived in November 2004 at the Quebec Arts Summit held in Montreal. More than 120 artists and other representatives of the English-speaking arts milieu, as well as government officials, came together to discuss ways to support artists and cultural workers in Quebec’s official language minority community (OLMC). With the support of sister organizations the Quebec Drama Federation (QDF), the Quebec Writers’ Federation (QWF), and the Association of English-Language Publishers of Quebec (AELAQ), ELAN was created to give a united voice to minority English-language artists of all backgrounds, working in all disciplines, and living in all regions of Quebec. Through networking events, a monthly email newsletter (ELANews), needs assessment surveys, and major projects such as the Arts Alive! Québec community festivals, ELAN has worked to bring Quebec artists closer together and spread their work far and wide.
Keywords: Official Language Minority Community (OLMC)

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de Chaudière-Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de l'Est-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de l'Estrie–CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de l'Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de l'Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de la Côte-Nord - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de la Gaspésie - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de la Montérégie-Centre - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de la Montérégie-Est - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de Lanaudière - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS de Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS du Centre Ouest de l'Île de Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles : Volume 1 : English-speaking Men and Fathers : RTS du Centre Sud de l'Île de Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. Volume 2 presents the same information for English-speaking women and mothers. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 1 : English-speaking Men and Fathers : RTS du Nord-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-Demographic Profiles Volume 1 : English-Speaking Men and Fathers : RTS du Saguenay–Lac-Saint-Jean - Pocock, Joanne (The Community Health and Social Services Network (CHSSN), 2016)
Volume 1 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the men and fathers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de Chaudière-Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de l'Est-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de l'Estrie – CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de l'Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de l'Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de la Côte-Nord - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de la Gaspésie - Pocock, Joanne (2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de la Montérégie-Centre - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de la Montérégie-Est - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de Lanaudière - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS de Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS des Îles - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS du Bas-Saint-Laurent - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS du Centre-Ouest-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2: English-speaking Women and Mothers : RTS du Centre-Sud-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2 : English-speaking Women and Mothers : RTS du Nord-de-l'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Gender Based Socio-demographic Profiles Volume 2 : English-speaking Women and Mothers : RTS du Saguenay – Lac-Saint-Jean - Pocock, Joanne (The Community Health and Social Services Network, 2016)
Volume 2 of these profiles draws from the 2016 Census of Canada to provide pertinent socio-demographic information on the women and mothers of Québec’s English-speaking communities by Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio- economic issues they face and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.

Regional Mini Portraits - Pocock, Joanne (2016)
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de Centre-Ouest-de-l’Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de Centre-Sud-de-l’Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de Chaudière-Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de l’Est-de-l’Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de l’Estrie – CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de l’Ouest-de-l’Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de l’Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de la Côte-Nord - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de la Gaspésie - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de la Montérégie-Centre - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de Lanaudiére - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS de Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of Children Aged 0 to 5 and their Parents - RTS du Nord-de-l’Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de Chaudière-Appalaches - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de l'Abitibi-Témiscamingue - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de l'Est-de-I'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de l'Estrie – CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de l'Estrie - CHU de Sherbrooke - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de l-Ouest-de-I'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de l'Outaouais - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de la Capitale-Nationale - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de la Côte-Nord - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de la Gaspèsie - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de la Montérégie-Centre - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de la Montérégie-Ouest - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de Lanaudière - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS de Laval - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS des Îles - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the children aged 0-5 of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS des Îles - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS des Laurentides - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS du Bas-Saint-Laurent - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS du Centre-Ouest-de-I'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS du Centre-Sud-de-I'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS du Nord-de-I'Île-de-Montréal - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Socio-demographic Profile of the Population Aged 65 and Over - RTS du Saguenay – Lac-Saint-Jean - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2016)
These profiles draw from the 2016 Census of Canada to provide pertinent socio-demographic information on the seniors aged 65 and over of Québec’s English-speaking communities and their families in accordance with Québec’s RTS (réseau territorial de services) territories. They include information on their numbers, where they live, family structures they are part of, socio-economic issues they face, their status as recent immigrants to Québec, aboriginal identity and their likelihood to be members of a visible minority. Each regional profile includes tables, graphs and information bullets that provide provincial and regional statistics for selected characteristics as well as comparisons between French-speaking majority and English-speaking minority populations within these administrative territories.
Keywords: Official Language Minority Community (OLMC)

Ahuntsic Cartierville : English-speaking Population 2016 / Ahuntsic Cartierville : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Anjou : English-speaking Population 2016 / Anjou : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Annual Report : 2015-2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Mercier Hochelaga-Maisonnneuve : English-speaking Population 2016 / Mercier Hochelaga-Maisonnneuve : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Montréal-Nord : English-speaking Population 2016 / Montréal-Nord : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Rivière-des-Prairies and Pointe-aux-Trembles : English-speaking Population 2016 / Rivière-des-Prairies and Pointe-aux-Trembles : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Rosemont La Petite-Patrie l'Est : English-speaking Population 2016 / Rosemont-La Petite-Patrie-l-est : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Rosemont La Petite-Patrie Nord : English-speaking Population 2016 / Rosemont La Petite-Patrie Nord : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Saint-Laurent : English-speaking Population 2016 / Saint-Laurent : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Saint-Léonard : English-speaking Population 2016 / Saint-Léonard : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Villeray–Saint-Michel–Parc-Extension : English-speaking Population 2016 / Villeray–Saint-Michel–Parc-Extension : Population d'expression anglaise 2016 - Réseau de l’est de l’île pour les services en anglais (REISA) (2016)

Focus Group Findings 2015-2016 - Seniors Action Quebec (SAQ) (2016)

2017-2018 Priorities of the English-speaking Community of Quebec and Annual Report of the Priority Setting Steering Committee - Strategic Priorities Forum (Quebec Community Groups Network (QCGN), 2016)
In September 2011, the Quebec Community Groups Networks launched The Strategic Priorities Forum, a standing five-year cyclical process to identify common priorities ensuring a vital and sustainable future for Quebec’s English-speaking communities and to collectively pursue enabling strategies to achieve community goals over five years. In this capacity, the QCGN established a nine-member Priority Setting Steering Committee (PSSC), a permanent Committee of QCGN’s Board of Directors, to assist the community with the governance of the Strategic Priorities Forum.

English-speaking Seniors : RTS de l'Estrie - CHUS - Townshippers' Association (2016)

The English-speaking Community of the Greater Quebec Region - Voice of English-speaking Quebec (VEQ) (2016)

McGill Program Networks Creating Impacts - Buffitt, Kimberly (2015)

The East Island Retention of Health Professionals Project – English, An Asset! : REISA Internships - A Success Story - Gatre Guemiri, Fatiha; Zappitelli, Juliana; Mirtaheri, Mina; Granner, Francine; Hendrickson-Nelson, Mary (2015)

[Letter to Premier Couillard re: English Schools / Lettre au premier ministre Couillard concernant les écoles anglaises] - Quebec Community Groups Network (QCGN) (2015)

Inter-regional Access to Specialized Health and Social Services for English-speakers from Eastern Quebec - Richardson, Mary (2015)
Keywords: Official Language Minority Community (OLMC)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2015)

Bilingualism Essential for Evolution of Our Laws and Access to Justice for English and French-speaking Minority Communities - Quebec Community Groups Network (QCGN) (2015)

Jennings Report Validates Minority Community Position on the Right to Management and Control of School Boards - Quebec English School Boards Association (QESBA); Quebec Community Groups Network (QCGN); English Parents Community Association (EPCA); Quebec Federation of Home and School Associations (QFHSA) (2015)

Building Community Capacity From Evidence to Action (2015-2016) : Profile of English-speaking Seniors : CLSC Manicouagan - Pocock, Joanne (Seniors Action Quebec (SAQ), 2015)
The Seniors Action Québec (SAQ) project is designed to mobilize English-speaking (ES) seniors (65+) and their communities in four regions of the province (Gaspésie, Greater Quebec City, Outaouais and the North Shore). This will be done by creating a network among English language regional community organizations to amplify the voice of minority language seniors and enhance their contribution to the vitality of their communities. The project will ready the network to identify critical issues affecting English-speaking seniors, establish regional action plans to address seniors’ priorities and to generally promote awareness of provincial and regional organizations serving the interests of the 65 years and over age group.

Building Community Capacity From Evidence to Action (2015-2016) : Profile of English-speaking Seniors : CLSC Territoire Naskapi - Pocock, Joanne (Seniors Action Quebec (SAQ), 2015)
The Seniors Action Québec (SAQ) project is designed to mobilize English-speaking (ES) seniors (65+) and their communities in four regions of the province (Gaspésie, Greater Quebec City, Outaouais and the North Shore). This will be done by creating a network among English language regional community organizations to amplify the voice of minority language seniors and enhance their contribution to the vitality of their communities. The project will ready the network to identify critical issues affecting English-speaking seniors, establish regional action plans to address seniors’ priorities and to generally promote awareness of provincial and regional organizations serving the interests of the 65 years and over age group.

Building Community Capacity From Evidence to Action (2015-2016) : Profile of English-speaking Seniors : CSSS de La Côte-de-Gaspé - Pocock, Joanne (Seniors Action Quebec (SAQ), 2015)
The Seniors Action Québec (SAQ) project is designed to mobilize English-speaking (ES) seniors (65+) and their communities in four regions of the province (Gaspésie, Greater Quebec City, Outaouais and the North Shore). This will be done by creating a network among English language regional community organizations to amplify the voice of minority language seniors and enhance their contribution to the vitality of their communities. The project will ready the network to identify critical issues affecting English-speaking seniors, establish regional action plans to address seniors’ priorities and to generally promote awareness of provincial and regional organizations serving the interests of the 65 years and over age group.

Building Community Capacity From Evidence to Action (2015-2016) : Profile of English-speaking Seniors : Rocher-Percé - Pocock, Joanne (Seniors Action Quebec (SAQ), 2015)
The Seniors Action Québec (SAQ) project is designed to mobilize English-speaking (ES) seniors (65+) and their communities in four regions of the province (Gaspésie, Greater Quebec City, Outaouais and the North Shore). This will be done by creating a network among English language regional community organizations to amplify the voice of minority language seniors and enhance their contribution to the vitality of their communities. The project will ready the network to identify critical issues affecting English-speaking seniors, establish regional action plans to address seniors’ priorities and to generally promote awareness of provincial and regional organizations serving the interests of the 65 years and over age group.

Brief to the Election System Study Panel: Minority Language Educational Rights and Canada's English Linguistic Minority Communities: Looking Forward - Quebec Community Groups Network (QCGN) (2015)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2015)

Inter-Regional Access to Specialized Health and Social Services for English-speakers from Eastern Quebec - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This project was developed to better understand the experience and needs of English speakers from the eastern regions of Quebec (Gaspésie - Îles-de-la-Madeleine, the North Shore, including the Lower North Shore, and the Lower Saint-Lawrence) as concerns extra-regional health and social services. The specific challenges facing this official language minority community were known only anecdotally, but needed to be better understood before effective action could be taken to address the needs of this population.
Keywords: Official Language Minority Community (OLMC)

The Thirty-Fourth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2015)

Quebec's English-speaking Communities Need Support to Integrate Newcomers - Quebec Community Groups Network (QCGN) (2015)
Keywords: Official Language Minority Community (OLMC)

CLC Evaluation – The Quest for Sustainability & Best Practices : Final Report - Qu'anglo (2015)

CLC Evaluation – The Quest for Sustainability & Best Practices : Final Report : Executive Summary - Qu'anglo (2015)

Youth Development Initiatives - Coasters Association (2015)
The Coasters Association has had many achievements over the years regarding youth initiatives, and priority areas have been identified. These achievements have contributed to the development and vitality of the region’s communities; however, there are many challenges that remain to hinder the future development and sustainability of the region.

Culture, Creativity, Confluence and Collision - Rodgers, Guy (2015)

Report : Community Network Forum - Community Health and Social Services Network (CHSSN) (2015)
Community organizations carry out their missions in an environment of continual reorganization of the health and social services system. In this context, groups must face the challenge of mobilizing resources to engage communities in a collective effort to commit the public system to meet the specific needs of community members. Groups are also challenged to introduce innovative approaches into their programs in a continual effort to achieve positive and long-lasting results.

The Policy on Language of Service - Jeffery Hale - Saint Brigid's (JHSB) (2015)
The objective of this policy is to ensure that employees communicate effectively with both French and English‐speaking clients and that Language Assistance Services are also available for other Limited‐French or English Proficient (LFEP) individuals and their surrogate decision‐makers at all points of contact, in a timely fashion and in their preferred language in order to ensure an understanding of their health condition and treatment options.

Language Access Policy : Planning & Implementation Guide - Prata, Ghislaine (Jeffery Hale - Saint Brigids (JHSB), 2015)
Jeffery Hale – Saint Brigid’s (JHSB) is a public, bilingual institution under participatory governance dedicated to providing safe, compassionate and high quality care. Among the strategic objectives of the organisation are the promotion of linguistic duality and openness to cultural diversity. Recognizing that language access is an integral component of the delivery of high quality and safe health services, JHSB has developed a number of policies, procedures and tools in the area of linguistic access. The organisation is currently seeking to consolidate and develop these initiatives within the framework of a comprehensive language access policy. This report provides a theoretical model and reference to practical tools to inform organisational efforts in the development of a language access policy and the implementation and continuous improvement of a language access plan.
Keywords: Official Language Minority Community (OLMC)

Portrait of the English-speaking Community of the Magdalen Islands - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2015)
This portrait has been completed in collaboration with many local partners, through the initiative of the Council for Anglophone Magdalen Islanders (CAMI), with support from the Community Health and Social Services Network (CHSSN). Other groups involved in this process include the municipality of Grosse-Ile, the Grosse-Ile school, the Community Economic Development and Employability Corporation (CEDEC), the Community Learning Centre (CLC), Agglomération des Îles (social development committee/Les Îles en Forme). The main objective of this portrait is to contribute to a more in-depth understanding of the English-speaking community of the Magdalen Islands in order to create a community development plan that addresses the issues it faces.

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2015)

Community Vitality Survey of the English-speaking Community of Quebec - Community Health and Social Services Network (CHSSN) (2015)

QCGN Satisfied Bill 10 Compromises Will Protect the Rights of English-speaking Communities - Quebec Community Groups Network (QCGN) (2015)

QCGN Worried Bill 10 Amendments Will Not Save Our Institutions - Quebec Community Groups Network (QCGN) (2015)

The McGill Retention Bursary Program: Evaluation Report : Training and Retention of Health Professionals Project - Gagnon, Marie-Pierre; Lampron, Amélie (CHU de Québec Research Centre, 2015)
An evaluation of this bursary program was conducted, focusing on the components of the program (e.g. eligibility criteria, selection process, etc.) and its outcomes (e.g. recipient intention to return to or stay working in a selected Quebec region at the end of their training, potential impact of the bursary program on retention of health professionals in English-speaking communities, etc.). The objectives of the evaluation were 1) to describe the current processes related to the functioning of the McGill Retention Bursary Program; 2) to explore recipients’ experience of this bursary program; 3) to explore community networks’ experience regarding their collaboration with this bursary program; 4) to assess the effectiveness of the bursary program; and 5) to propose potential improvement strategies for the bursary program currently in place.

Quebec's English-speaking Populations According to the 2011 National Household Survey and the 2011 Census of Canada - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2015)
This report presents tables on the size, proportion and age structure of the English-speaking populations of Quebec at various levels of health geographies. The information is drawn from two Statistics Canada surveys, namely, the 2011 National Household Survey (NHS) and the 2011 Census of Canada (Census). This document is intended to: provide an easy reference point for information on population size, proportion and age structure; clarify the variances in the population count and percentages that arise from the different sampling strategies of the Census and National Household Survey. The report consists of two tables, namely: An overview of Quebec and the RSS regions, showing Census and NHS populations counts; A detailed table, showing Census and NHS population counts for CSSS and CLSC territories.
Keywords: Official Language Minority Community (OLMC)

Public Readings by Authors Published by Members of the Association of English-Language Publishers of Quebec (AELAQ) - Association of English-language Publishers of Quebec (AELAQ) (2015)

Public Readings by Authors Published by Members of the Association of English-Language Publishers of Quebec (AELAQ) : Extended - Association of English-language Publishers of Quebec (AELAQ) (2015)

Action Framework : Supporting the Well-Being of Minority English-Language Youth, Schools and Communities - Community Health and Social Services Network (CHSSN) (2015)

Community NetLink - Community Health and Social Services Network (CHSSN) (2015)

2014-2015 Funded Projects - Dialogue McGill (2015)

Partnering for the Well-being of Minority English-Language Youth, Schools & Communities - Gonsalves, Allison; Kueber, Russell; Langevin, Paule; Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2015)
This document identifies some of the unique challenges, strengths, and aspirations of English-speaking youth in Quebec and provides a school and community-based framework for action intended to have a positive impact on their well-being and educational success. It emerges from the collaboration of community health and social services networks, called (NPIs) - abbreviation for the Networking and Partnership Initiative and Community Learning Centers (CLCs) seeking to improve the overall well-being of minority language youth residing in province.
Keywords: Official Language Minority Community (OLMC)

Blazing a Trail for Active and Healthy Aging: An Action Plan for Quebec’s English-speaking Seniors 2010-2015 / Tracer la voie pour vieillir en santé et demeurer actif : Plan d’action à l’intention des aînés d’expression anglaise du Québec 2010-2015 - Quebec Community Groups Network (QCGN) (2015)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2015)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2015)

Annual Report : 2014-2015 - Réseau de l’est de l’île pour les services en anglais (REISA) (2015)

Quebec and Us : A Mutation of Identity - Rodgers, Guy (Diversité Artistique Montréal (DAM), 2015)

Measure 2 : Retention Program : Community Networks and Educational Institutions Components : Prospectus 2014-2018 - Dialogue McGill (2014)
In conformity with the Implementation Framework, this Prospectus addresses Measure 2, the 2014-2018 Retention Program – Community Networks and Educational Institutions Components. McGill University prepared this Prospectus to support the calls for proposals for retention initiatives from the community networks and educational institutions. It presents the structure and content of each of these components of the Program, the objectives, the partners involved, the conditions to be fulfilled, the parameters of the call for proposals and the funding structure. It deals with training and retention incentive initiatives and support measures for students, more specifically promotional projects with health and social services institutions and educational institutions, allocation of bursaries, initiatives to support internship supervisors, professional French language courses for students in the targeted educational institutions, welcoming and community integration measures, language and cultural adaptation activities for professionals from the health and social services network, and outreach activities with extra-regional partners to support the integration and academic success of students studying out of region.

Thousands of Quebecers Sign Petitions Seeking Changes to Bill 10 - Quebec Community Groups Network (QCGN) (2014)

Community Leaders Demand Major Changes to Bill 10 - Quebec Community Groups Network (QCGN) (2014)

English-speaking Quebecers Like to See Themselves Reflected on CBC - Quebec Community Groups Network (QCGN) (2014)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2014)

QCGN Presents its Brief on Bill 10 - Quebec Community Groups Network (QCGN) (2014)

Letter of Support for QCGN - Zucchi, John (2014)

[Letter re: Bill 10 - Letters of Support of QCGN] - Committee for Anglophone Social Action (CASA); Coasters Association; Community Health and Social Services Network (CHSSN); Jeffery Hale - Saint Brigid's (JHSB); Neighbours Regional Association of Rouyn-Noranda; Quebec Community Groups Network (QCGN); Quebec Federation of Home and School Associations (QFHSA) (2014)

[Letter Regarding Bill 10 from QCGN President] - DePoe, Lawrence (2014)

Moving Forward : Building Research Capacity Related to Quebec's English-speaking Seniors - Quebec Community Groups Network (QCGN) (Quebec Community Groups Network (QCGN), 2014)
We are grateful to the Government of Quebec who funded the project through the Soutien aux initiatives visant le respect des aînés (SIRA) program. We’d like to acknowledge the project Steering Committee who demonstrated ongoing dedication and commitment to the project. Members are: David Cassidy, president of Seniors Action Quebec and committee co-chair; Sylvia Martin-Laforge, director general at QCGN and committee co-Chair; Cheryl Henry-Leggo, Vision Gaspé-Percé Now; Kevin Erskine-Henry, chair, South Shore Community Partners Network; Premela Pearson, secretary, Indian Women’s Circle; Jim Colmer, residepnt, James Colmer Consultation Inc; Jan Anderson-Toupin, Jeffery Hale; Al Abdon, Filipino Association of Montreal and Suburbs. The QCGN contracted Dr. Joanne Pocock as the lead researcher on this project. The project has deeply benefited from her guidance, professionalism and intellectual rigour.
Keywords: Official Language Minority Community (OLMC)

English-speaking Community Excluded from Debate on Bill-10 - Quebec Community Groups Network (QCGN) (2014)

QCGN Launches Most up-to-date, Detailed Portrait of Quebec's English Speaking Seniors - Quebec Community Groups Network (QCGN) (2014)

Retention Program for the McGill University Training and Retention of Health Professionals Project : Evaluation of the retention program measure and recommendations - Gagnon, Marie-Pierre (Dialogue McGill, 2014)
This report presents an evaluation of the activities implemented under the Retention Program, in relation to the Support for Health and Social Services Institutions and Support for Educational Institutions in order to highlight the main strengths and areas for improvement. The mandate was to identify strategies that could help to increase the impact of the internship program on the retention of health and social services professionals in the health and social services network. The evaluation would then contribute to the ongoing improvement of this program, by providing some direction to guide the actions of those responsible for the McGill University Training and Retention of Health Professionals Project and project partners.

English-speaking Community Very Concerned About Barrette Reform Bill - Quebec Community Groups Network (QCGN) (2014)

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2014)

QCGN Concerned About Vitality of English-speaking Communities and Quebec as a Whole - Quebec Community Groups Network (QCGN) (2014)

The Thirty-Third Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2014)

Community in Movement Forum - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)

QCGN Applauds Premier's Message of Inclusion and Diversity - Quebec Community Groups Network (QCGN) (2014)

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Ahuntsic (06132) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Anjou (06044) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Arthabaska (04081) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Avignon (11012) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Aylmer (07012) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Beauce Sartigan (12031) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Beauport (03032) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Bonaventure (11011) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Bordeaux Cartierville (06111) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Brossard Saint Lambert (16052) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Cap de la Madeleine (04052) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Chambly Carignan Marieville (16072) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Charlesbourg (03034) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Chateauguay Mercier (16041) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Chaudiere (12022) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Chomedey (13012) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Cote des Neiges (06071) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Cote Saint Luc (06081) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC D'autray (14011) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Desjardins (12021) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Dollard des Ormeaux (06013) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Duberger Les Saules Lebourgneuf (03026) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Duvernay (13011) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Gaspe (11031) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Gatineau (07013) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Hochelaga Maisonneuve (06052) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Hull (07011) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Joliette (14013) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC L'Assomption (14022) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Lac Saint Louis (06011) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Lachine (06021) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Lajemmerais (16063) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Lasalle (06022) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Laurentien (0603) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC les Jardins de Napierville (16042) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC les Maskoutains (16082) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Les Moulins (14021) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Limoilou-Vanier (03025) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Longueuil Est (16062) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Longueuil Ouest (16061) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Loretteville Val Belair (03031) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Matawinie (14012) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Mercier Est (06043) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Metro (06074) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Mont Royal (06073) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Montcalm (14014) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Montreal Centre Sud (06092) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Montreal Centre Ville (06094) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Montreal Nord (06131) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Notre Dame de Grace (06082) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Olivier Guimond (06051) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Orleans (03033) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Parc Extension (06075) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Petite Nation (07052) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Petite Patrie (06122) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Pierrefonds (06012) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Plateau Mont Royal (06093) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Pointe aux Trembles (06042) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Pointe Saint Charles (06031) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Pont Viau (13013) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Quebec-Basse-Ville (03024) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Quebec-haute-ville (03023) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Riviere des Prairies (06041) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Rosemont (06053) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Saint Bruno Beloeil Saint Hilaire (16081) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Saint Constant la Prairie (16043) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Saint-Henri (06034) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Saint Hubert (16051) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Saint Jean sur Richelieu Saint Luc (16071) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Saint Laurent (06112) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Saint Leonard (06061) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Saint Louis du Parc (06091) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Saint Michel (06062) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Saint Paul (06033) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Sainte-foy-Sillery (03022) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Sainte Rose de Laval (13014) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Snowdon (06072) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Trois Rivieres (04051) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Vallee de la Lievre (07051) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Verdun (06032) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Villeray (06121) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS 0101 - Rimouski-Neigette - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS Cavendish (0608) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS Champlain (1605) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS Chicoutimi (0202) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS Cleophas-Claveau (0201) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS d'Ahuntsic et Montreal Nord (0613) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS d'Antoine Labelle (1504) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Arthabaska Erable (0408) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Baie des Chaleurs (1101) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Beauce (1203) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Becancour Nicolet Yamaska (0406) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Bordeaux Cartierville Saint Laurent (0611) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Dorval Lachine Lasalle (0602) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Drummond (0407) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Gatineau (0701) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de L'Energie (0403) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de l'Quest de l'Isle (0601) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de la Basse Cote Nord (0907) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de la Haute Yamaska (1611) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de La Montagne (0607) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de la MRC de Coaticook (0505) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de la Pointe de l'Ile (0604) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de la Region de Thetford (1204) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de la Vallee de la Gatineau (0704) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de la Vallee de lor (0806) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Manicouagan (0902) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Memphremagog (0506) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Papineau (0705) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Portneuf (0301) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Rouyn Noranda (0803) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Saint Jerome (1502) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Saint Leonard et Saint Michel (0606) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Sept Iles (0903) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Sorel Tracy (1609) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de St Therese de Blainville (1503) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Temiscaming et de Kipawa (0801) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Trois Rivieres (0405) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Vaudreuil Soulanges (1612) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS des Collines (0703) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS des d'Argenteuil (1507) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS des Iles (1104) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS des Pays d'en Haut (1505) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS des Sommets (1506) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS Des Sources (0502) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS du Coeur de l'Ile (0612) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS du Grand Littoral (1202) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS du Haut Saint Laurent (1602) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS du la Cote de Gaspe (1103) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS du Lac des Deux Montagnes (1501) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS du Lac Temiscamingue (0802) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS du Nord de Lanaudiere (1401) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS du Pontiac (0702) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS du Rocher Perce (1102) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS du Sud de Lanaudiere (1402) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS du Sud Ouest Verdun (0603) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS du Suroit (1603) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS du Val Saint Francois (0504) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS Haut Richelieu Rouville (1607) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS Haut Saint Francois (0503) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS Haut Saint Maurice (0401) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS Institut Universitaire Geriatrie Sherbrooke (0507) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS Jardins Roussillon (1604) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS Jeanne Mance (0609) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS Jonquiere (0203) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS la Pommeraie (1610) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS Naskapi (0908) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS Pierre Boucher (1606) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS Quebec-nord (0303) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS Richelieu Yamaska (1608) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS Vieille-capitale (0302) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

VEQ Newsletter - Voice of English-speaking Quebec (VEQ) (2014)

Community NetLink - Community Health and Social Services Network (CHSSN) (2014)

Community NetLink - Community Health and Social Services Network (CHSSN) (2014)

Brief Submitted to La commission de la santé et des services sociaux de l'Assemblée nationale du Québec Concerning Bill 10, An Act to Modify the Organization of the Health and Social Services Network, in Particular by Abolishing the Regional Agencies - Quebec Community Groups Network (QCGN) (2014)

Moving Forward : Building Research Capacity Related to Quebec’s English-speaking Seniors : Executive Summary - Quebec Community Groups Network (QCGN) (2014)
While Quebec’s English-speaking seniors share many of the same needs and priorities as their French-speaking counterparts, as an official linguistic minority community (OLMC) they also have needs and priorities that are unique within the broader senior population. While there has been a great deal of research on Quebec’s demographic shift and its senior population, little - if - any attention has been paid to the specific needs and priorities of Quebec’s English-speaking seniors who are an official language minority community in Canada. One notable exception is the recent 2013 report entitled ‘Enjoying your senior years in your own language’ for the Office of the Commissioner for Official Languages, which employed 2006 Canadian census figures.

Annual Report : 2013-2014 - Réseau de l’est de l’île pour les services en anglais (REISA) (2014)

Federal Institutions Must Properly Support Quebec's English-speaking Seniors, says Graham Fraser - Office of the Comissioner of Official Languages (2013)

English-speaking Seniors Unite to Create Provincial Vote - Seniors Action Quebec (2013)

Commissioner's Findings Confirm Concerns of English-speaking Quebec - Quebec Community Groups Network (QCGN) (2013)

Jeffery Hale - Saint Brigid's at a Glance - Jeffery Hale - Saint Brigid's (JHSB) (2013)

One Size Does Not Fit All: Distinct Solutions for Distinct Needs - Advisory Board on English Education (2013)
In this report to the Minister, the Advisory Board on English Education is taking the opportunity to review the themes and concerns identified in earlier correspondence, reports and briefs that continue to describe English education in Québec accurately, and to update them with current examples of both concerns and successes. We emphasize that there is no intention to promote one system over another, nor to assign fault. We believe that many of the inherent difficulties faced by English school boards, schools and centres could be mitigated if MELS were to take better account of the differences between the two sectors in its policies and their implementation. It is hoped that a description of the distinctiveness of the English sector and how it functions differently from the French sector will provide some insight as to how the English system is frequently constrained by many of the Ministry’s policies, especially in their application, and indicate the need for flexibility in implementing policy. This will ensure that the English education system can continue to prepare its graduates to participate fully in the life of Québec society.

Language Training Program : Overall Profile 2009-2013 : Discussion Guide - Dialogue McGill (2013)

ACDPN Proposes Roadmap for Access to Prevention Services for Black English-speaking Families - African Canadian Development and Prevention Network (2013)

QCGN Congratulates Shelly Glover New Minister for Canadian Heritage and Official Languages - Quebec Community Groups Network (QCGN) (2013)
Keywords: Official Language Minority Community (OLMC)

Language Training Program : Overall Profile 2009-2013 - Dialogue McGill (2013)
The Language Training Program, Measure 1, has three components. The first two pertain to English and French for professional purposes courses offered through the regional language training projects designed and implemented by Quebec’s 18 health and social services agencies (the "agencies"). The third covers support activities for the trainers giving language courses in the regions and the learners who take those courses. These activities are developed and offered by the McGill Project team. The Program structure and content were developed by the McGill Project team and are described in Language Training Program – Frame of Reference 2009-2013, which also describes the target users; the Program objectives, partners and conditions; the parameters of the call for proposals for regional training projects; and regional allocation of the funding envelope. A coordinating mechanism, the MSSS-McGill Joint Committee, implements and monitors the Program, as prescribed in the Implementation Framework that the two organizations signed onto in November 2009.

Training and Retention of Health Professionals Project : Research development program : overall profile 2009-2013 - Dialogue McGill (2013)
The McGill University Training and Retention of Health Professionals Project (McGill Project) adds to the initiatives of the Government of Québec to give English-speaking Quebecers access to the full range of health and social services in their own language. It is an additional tool for implementing and revising regional programs for access to services in English, as prescribed in the Act respecting health services and social services. The McGill Project addresses the recognized needs of English-speaking communities and the challenge that those needs pose for Quebec's health and social services system. Given this, the McGill Project set up various programs to train and promote the hiring and retention of sufficient professionals qualified to deliver health and social services in English. The McGill Project is funded by Health Canada in the amount of $19 million over four years through its Official Languages Health Contribution Program (OLHCP). This report is the third in a three-part series to present the data gathered through the McGill Project from 2009 to 2013. The series deals with the three measures of the McGill Project, namely, the Language Training Program, the Retention and Distance Professional and Community Support Program, and the Research Development Program. The reports are organized to reflect the structure of each program as set out in the reference documents. Each report begins with an introduction of the program, then briefly describes the variables, data sources and sections of the report. This document reports on Measure 3, the Research Development Program, and is meant to inform Program reframing in Phase 3 (2013-2018).

Training and Retention of Health Professionals Project : Retention program : overall profile 2011-2013 - Dialogue McGill (2013)
The McGill University Training and Retention of Health Professionals Project (McGill Project) adds to the initiatives of the Government of Québec to give English-speaking Quebecers access to the full range of health and social services in their own language. It is an additional tool for implementing and revising regional programs for access to services in English, as prescribed in the Act respecting health services and social services . The McGill Project addresses the recognized needs of English-speaking communities and the challenge that those needs pose for Quebec's health and social services system. Given this, the McGill Project set up various programs to train and promote the hiring and retention of sufficient professionals qualified to deliver health and social This report is the second in a three-part series to present the data gathered through the McGill Project from 2009 to 2013. The series concerns the three measures of the McGill Project, namely, services in English. The McGill Project is funded by Health Canada in the amount of $19 million over four years through its Official Languages Health Contribution Program (OLHCP). the Language Training Program, the Retention and Distance Professional and Community Support Program, and the Research Development Program.

CRTC Must Oblige Vidéotron to Restore English-language Community Television Station - Quebec Community Groups Network (QCGN) (2013)

CRTC Must Oblige Vidéotron to Restore English-language Community Television Station : Attention News Directors, Television, and Arts Reports - Quebec Community Groups Network (QCGN) (2013)

English-speaking Community Needs Formal Presence in Provincial Government, says QCGN members - Quebec Community Groups Network (QCGN) (2013)

QCGN Marks End of Notre Home Tour with Benefit Concert for Kids Help Phone - Quebec Community Groups Network (QCGN) (2013)

Canada, Bilingualism and Trade - Arcand, Alan; The Conference Board of Canada (Community Economic Development and Employment Corporation (CEDEC), 2013)
The French language is one of the world’s major languages. According to L’Organisation internationale de la Francophonie (OIF), at least 220 million people in the world speak French. It’s the official language of all United Nations agencies and a large number of international organizations. The language originated in France and spread by way of the country’s overseas expansion. Today, some 30 countries in the world, including Canada, have recognized French as an official language.

CRTC Decision on CBC License Renewal Good News for English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2013)
Keywords: Official Language Minority Community (OLMC)

CRTC Decision on CBC License Renewal Good News for English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2013)

QCGN Calls for Productive Dialogue with English-speaking Community - Quebec Community Groups Network (QCGN) (2013)

QCGN Opening Remarks to Committee on Culture and Education : General consultation and public hearings on Bill 14: An Act to Amend the Charter of the French Language, the Charter of Human Rights and Freedoms and Other Legislative Provisions - Quebec Community Groups Network (QCGN) (2013)

Community Portrait : Sutton - Richardson, Mary; Jobson, Shirley (Community Health and Social Services Network (CHSSN), 2013)
In 2009, the Community Health and Social Services Network (CHSSN) concluded an agreement with Quebec’s Institut national de santé publique (INSPQ) to develop knowledge on the English-speaking population of Quebec as part of a program concerning health projects for offi cial language minority communities. Gaining a better understanding of English-speaking communities in Quebec is one of the objectives of that collaboration, and it is explored here through the lens of community development.
Keywords: Official Language Minority Community (OLMC)

Report : Future Forum of the English-speaking Community - Future Forum of the English-speaking Community (Voice of English-speaking Quebec (VEQ), 2013)
The Future Forum was held on November 24th, 2012 from 9 am - 2 pm at Eastern Québec Learning Center in Quebec City, Québec. The purpose of the event was to share opinions on the current state, needs and challenges of the English-speaking community while generating a shared vision for our future.

QCGN Approves New Roadmap for Canada's Official Languages - Quebec Community Groups Network (QCGN) (2013)

Quebec Federation of Home & School Association (QFHSA) Defends its Brief on Bill 14 Before the Quebec National Assembly - Quebec Federation of Home and School Associations (QFHSA) (2013)

Federal Budget Indicates Government Comitted to Quebec's English-speaking Minority with a Renewed Roadmap for Official Languages - Quebec Community Groups Network (QCGN) (2013)

QCGN Leaders Disappointed by CAQ's Position on Bill 14 - Quebec Community Groups Network (QCGN) (2013)

Brief Submitted to the National Assembly of Quebec’s Committee on Culture and Education by the English Language Arts Network for the General Consultation and Public Hearings on Bill 14 : An Act to Amend the Charter of the French Language, the Charter of Human Rights and Freedoms and Other Legislative Provisions - English Language Arts Network (ELAN) (2013)
This brief was prepared by the English-Language Arts Network (ELAN), an incorporated not-for-profit organisation that represents 8,000 English-speaking artists in Quebec. ELAN is a meeting place for English-language artists and cultural workers of all disciplines from every region of Quebec, where they can share expertise and resources, build audiences and alliances, seek support, advocate for their interests, and make common cause with the Francophone arts community.

Brief Presented to the National Assembly’s Committee on Culture and Education with Regards to General Consultation and Public Hearings on Bill 14: An Act to Amend the Charter of the French Language, the Charter of Human Rights and Freedoms and Other Legislative Provisions - Quebec Community Groups Network (QCGN) (2013)
This brief was prepared by the Quebec Community Groups Network (QCGN), an incorporated not-for-profit organization that identifies, explores and addresses strategic issues affecting the development and vitality of English-speaking Quebec. The QCGN and its 41 members work cooperatively and in partnership with community stakeholders, leaders, governments and institutions, to advance the interests of our minority community.

Brief Regarding the General Consultation and Public Hearings on Bill 14 : An Act to Amend the Charter of the French Language, the Charter of Human Rights and Freedoms and Other Legislative Provisions - Voice of English-speaking Quebec (VEQ) (2013)
The purpose of this brief is to highlight the potential impacts that the proposed Bill 14 could have on the minority English-speaking community of the Greater Quebec City region. As the preeminent interest group representing English-speakers in the Quebec City region, VEQ has carefully analyzed all the modifications included in the proposed Bill 14 and has consulted its membership, community and many of its key partners in order to present this comprehensive evaluation of the impacts that Bill 14 could have on our community. It is our opinion that Bill 14, if adopted in its present form, will have several negative consequences on the vitality of our community and on the capacity of English speakers to continue to be contributing citizens of our region. In addition, we sincerely believe that Bill 14 will also have a real negative impact on the capacity of our entire region to attract and retain English-speaking immigrants and migrants which will directly affect the economic prosperity of the Quebec City region.
Keywords: Official Language Minority Community (OLMC)

Baseline Data Report 2012-2013 : Quebec's English-speaking Community Networks and their Partners in Public Health and Social Services - Pocock, Joanne (Community Health and Social Services Network, 2013)
The 2012-2013 BDR reports unpon the nature and development of the partnerships that CHSSN Networking and Partnership Initiative (NPI) networks have established in their regions. The report represents the experience, thoughts, and observations - the collective wisdom - of the NPI networks on a range of topics related to their partnerships. The report looks back at the work incolved in partnering since the genesis of CHSSN, the ongoing challenges and successes, and the perceived impact of partnering on the NPI communities and their access to health and social services in English.
Keywords: Official Language Minority Community (OLMC)

QCGN Board of Directors : Resolution Regarding Bill 14, An Act to Amend the Charter of the French Language, the Charter of Human Rights and Freedoms and other Legislative Provisions, Tabled in the National Assembly of Quebec on December 5, 2012 - Quebec Community Groups Network (QCGN) (2013)

Improving Access to Health and Social Services for Quebec’s English-speaking Population : Development Priorities 2013-2018 - Udy, Michael; Howarth, Kelly; Kischuk, Nathalie; Medeiros, CMA (Community Health and Social Services Network (CHSSN), 2013)
This report has been prepared at the request of the Community Health and Social Services Network (CHSSN). It is intended for presentation to Health Canada in the context of the renewal of the Federal Government’s commitments to official language minority communities (OLMCs) for the period 2013-2018. The report presents development priorities for the improvement of access to health and social services in English for Quebec’s English-speaking communities as identified by the personnel of organizations work- ing on this issue.

Improving Access to Health and Social Services for Quebec’s English-speaking Population: Development Priorities 2013-2018 : A Companion Document - Udy, Michael; Howarth, Kelly; Kischuk, Nathalie; Medeiros, CMA (Community Health and Social Services Network (CHSSN), 2013)
This document has been prepared at the request of the Community Health and Social Service Network (CHSSN). It is the companion document to Improving Access to Health and Social Services for Quebec’s English- Speaking Population, Development Priorities 2013-2018, also prepared at the request of the CHSSN. Both are intended for presentation to Health Canada in the context of the renewal of the Federal Government’s com- mitments to official linguistic minorities for the period 2013-2018. These commitments have been funded to date under the Roadmap for Canada’s Linguistic Duality 2008-2013 (the Roadmap). More about the context of the project is presented in Appendix I.

English-speaking Seniors in Quebec - Canada. Office of the Commissioner of Official Languages (2013)

Community NetLink - Community Health and Social Services Network (CHSSN) (2013)

Les Québécois auraient besoin d’un nouveau contrat linguistique : Le rapiéçage, comme pour le projet de loi 14, est désuet / Quebecers Need a New Linguistic Social Contract : Piecemeal Approaches Like Bill 14 Are Outdated - D'andrea, Giuliano; Smith, Richard (2013)

Annual Report : 2012-2013 - Réseau de l’est de l’île pour les services en anglais (REISA) (2013)

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2013)

The Thirty-Second Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2013)

The Decline of the English School System in Quebec - Bourhis, Richard Y.; Foucher, Pierre (Canadian Institute for Research on Linguistic Minorities (CIRLM), 2012)
With the adoption of the Charter of the French Language by the Parti Québécois in 1977, Quebec Anglophones were most concerned about the erosion of their educational institutions resulting not only from the out-migration of Anglophones and Allophones to the rest of Canada (ROC), but also from the Bill 101 law stipulating that international immigrants to Quebec could no longer choose to send their children to English schools (Mallea, 1984). Thus, following Bill 101, Quebec Anglophones could no longer count on immigrants to maintain the demographic base necessary to keep open key English medium schools across the province (McAndrew, 2002). However by 1982, Anglophones, as English mother tongue “rights holders”, could now count on their right to English schooling in Quebec as enshrined in Article 23 of the Canadian Constitution.

Community Portrait of Bonne-Espérance - Richardson, Mary (Community Health and Social Services Network (CHSSN), 2012)
In 2009, the Community Health and Social Services Network (CHSSN) concluded an agreement with Quebec’s Institut national de santé publique (INSPQ) to develop knowledge on the English-speaking population of Quebec as part of a program concerning health projects for official language minority communities. Gaining a better understanding of English-speaking communities in Quebec is one of the objectives of that collaboration, and it is explored here through the lens of community development.
Keywords: Official Language Minority Community (OLMC)

Community Portrait : New Carlisle - Richardson, Mary; Gauvin-Racine, Joëlle (Community Health and Social Services Network (CHSSN), 2012)
In 2009, the Community Health and Social Services Network (CHSSN) concluded an agreement with Quebec’s Institut national de santé publique (INSPQ) to develop knowledge on the English-speaking population of Quebec as part of a program concerning health projects for official language minority communities. Gaining a better understanding of English-speaking communities in Quebec is one of the objectives of that collaboration, and it is explored here through the lens of community development.
Keywords: Official Language Minority Community (OLMC)

The Thirty-First Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2012)

Info-liens / Info-link : CHSSN’s info-links for researchers interested in addressing the topic of improving the health and well-being of English-speaking minority communities in Québec - Community Health and Social Services Network (CHSSN) (2012)
Keywords: Official Language Minority Community (OLMC)

Declaration from the Community Priority Setting Conference of the English-Speaking Community of Quebec - Quebec Community Groups Network (QCGN) (2012)

Regional Development of English Language Entrepreneurial Services - Qu'anglo (Youth Employment Services (YES), 2012)
YES is a non-profit organization that provides English language employability and entrepreneurship services in Quebec, principally those on the Island of Montreal. The areas of services offered are job search, entrepreneurship, mentorship and artists’ programs. In response to requests from the organizations in the regions outside of Montreal for similar services, YES has begun to develop support and delivery mechanisms that respond to the unique needs of the regions1 within a context of building economic viability. This report provides the results of the work carried out in 2011-12 to look at the feasibility of offering YES-type services in the regions, as well as the planning and development activities that should be carried out to support a broader economic development amongst English-speaking communities in Quebec.
Keywords: Official Language Minority Community (OLMC)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2012)

In the Know : Identifying Multiple Aspects of Quebec's Community Sector - Centre des organismes communautaires / Centre for community organizations (2012)
In October of 2008, The Centre for Community Organizations (COCo) began a community research project to help develop a better understanding of the diversity of groups working for social change in Québec. The study, “In the Know: Identifying multiple aspects of Québec’s community sector”, was supported by the Secretariat à l’Action Communautaire Autonome et aux Initiatives Sociales (SACAIS) and aimed to survey English-speaking, bilingual and ethno-cultural community groups across Québec over a three year period. The research was carried out between 2009 and 2012.

The Literacy and Essential Skills Needs of Quebec's Anglophone Adults - Centre for Literacy (CFL) (2012)
Understanding the Literacy and Essential Skills Needs of Quebec’s Anglophone Adults,1 Phase 1, was a project designed to deepen knowledge and understanding of the literacy and essential skills (LES) needs of Anglophone adults living in Quebec as a basis to more effectively serve Englishspeaking communities across the province. The issue was first identified in a publication by Statistics Canada of the 2003 IALSS results for Canada’s official language minorities (discussed in detail in Sections Three and Four) which showed large disparities in literacy performance among Quebec Anglophones (Corbeil 2006: 20). The findings suggested differences in needs from one community to another that may require targeted services.

Community NetLink - Community Health and Social Services Network (CHSSN) (2012)

Community NetLink - Community Health and Social Services Network (CHSSN) (2012)

English Health Partnership Annual Report 2011-2012 - Neighbours Regional Association of Rouyn-Noranda (2012)

Baseline Data Report 2011-2012 : Socio-Economic Profiles of the English-speaking Visible Minority Population by Quebec Health Region - Pocock, Joanne (Community Health and Social Services Network, 2012)
The Baseline Data Report series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well being of their constituencies.
Keywords: Official Language Minority Community (OLMC)

School Boards and Local Autonomy : Resolution 2012/1 - Quebec Federation of Home and School Associations (QFHSA) (2012)

Annual Report : 2011-2012 - Réseau de l’est de l’île pour les services en anglais (REISA) (2012)

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2012)

[Letter for St Gabriel School] - McDaid, Mary (2011)

Young Quebec Artists Encouraged to Turn their Passion into Profit - Youth Employment Services (YES) (2011)

Community Network Forum : Addressing Mental Health Issues : An Emerging Challenge for Community Resources - Réseau de l’est de l’île pour les services en anglais (REISA) (2011)
The forum will address the challenges that community resources face as an increasing number of those seeking their services show signs of psychological distress and poor mental health. What is the impact of this emerging clientele on community programs? Where do community resources refer persons in difficulty? How should programs be adapted to address the new challenge? What are the policy and program responses of government and the public health and social services?

Language Training Program : Frame of Reference 2010-2013 - Dialogue McGill (2011)
The McGill Training and Retention of Health Professionals Project seeks to contribute to Government of Quebec initiatives aimed at ensuring that English-speaking Quebecers have access to the full range of health and social services in their language. To this end it proposes a series of measures to train, hire and retain an adequate workforce for delivering health services and social services in English. The Project objectives are to a) improve the capacity of the health and social services network to serve English speakers in their language and b) increase the participation of English-speaking professionals in Quebec’s health and social services system. The achievement of these goals depends on a solid partnership between McGill University and the ministère de la Santé et des Services sociaux (MSSS). A MSSS-McGill joint committee has been formed to oversee the implementation and monitoring of the various Project measures.

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2011)

New Online Service Makes Expert Advice Accessible and Affordable - Youth Employment Services (YES) (2011)

Understanding Literacy and Family Literacy Needs of Anglophone Adults in Quebec : Research Summaries - The Centre for Literacy of Quebec (CFL) (2011)
The Understanding literacy and family literacy needs of Anglophone adults in Quebec project aimed to deepen knowledge and understanding of the literacy and essential skills (LES) needs of Anglophone adults living in Quebec as a basis to more effectively serve English-speaking communities across the province. The issue was first identified in a publication by Statistics Canada of the 2003 IALSS results for Canada’s official language minorities which showed large disparities in literacy performance among Quebec Anglophones. The findings suggested differences in need from one community to another that may require targeted services. This project set out to fill this knowledge gap and to insert LES into the ongoing discussion about Anglophones in Quebec. All Quebec English-language umbrella groups stand to benefit from the findings in terms of proposing better policy, planning new services and using resources more efficiently. There may be opportunities for new partnerships to develop solutions to some challenges not previously seen as linked to literacy. The project will also provide a useful road map for identifying promising new research avenues that would assist LES organizations in getting a more detailed picture of the communities they are aiming to serve.

Access to Health and Social Services : A Comparison of French & English-language CROP-CHSSN Survey Samples - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2011)
The Baseline Data Report (BDR) is a report developed to serve as a resource that will allow NPI communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well being of their constituencies. There is now a series of inter‐related Baseline Data Reports (see below) which may be accessed through the CHSSN website (www.chssn.org).
Keywords: Official Language Minority Community (OLMC)

Briefs Submitted to the Minister of Education, Recreation and Sports : 2011 - Advisory Board on English Education (2011)

Community Health Education Program (CHEP) : 2010-2011 - Community Health and Social Services Network (CHSSN); McGill University Health Centre (2011)
The Community Health Education Program (CHEP) is a dynamic program that facilitates distance community learning of health and social information for English-speaking Quebecers in remote communities, via five different components: videoconferencing, telephone conferencing, videoconferencing Session DVD’s, community radio (Internet access), follow-up activities (face-to-face)

The Thirtieth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2011)

Baseline Data Report 2010-2011 : English-language Health and Social Services Access in Quebec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2011)
The 2010-2011 Baseline Data Report relays the health and social service findings of the 2010 CHSSN-CROP Survey on Community Vitality Survey and compares them with the findings of the 2005 survey. In order to facilitate the five year comparison the design of the present report reproduces, as much as possible, that of the 2005-2006 BDR. The commonalities and distinct features of regional communities within the English-speaking provincial population are delineated as well as sub-groups defined by gender, age, household income, health status and level of bilingualism. While this report is limited to the health and social service sector, the Survey on Community Vitality also collects the opinions, perceptions and expectations of a representative sample of English-speaking Quebecers in each region of Quebec with respect to issues in education, manpower development, culture and communications. The 2010 study replicates a previous survey conducted by CROP in 2000 for the Missisquoi Institute and again in 2005 for the CHSSN. A survey was also done among a representative sample of French-speaking Quebecers on the same issues. These results are not presented in this report.
Keywords: Official Language Minority Community (OLMC)

A Community Dialogue About Retention and Integration of Newcomers to the English-speaking Communities of Quebec - Quebec Community Groups Network (QCGN) (2011)

Linda Leith Remarks to OCOL Part VII Forum - Leith, Linda (2011)
Keywords: Official Language Minority Community (OLMC)

Marking Milestones - English Language Arts Network (ELAN) (2011)

Fostering Student Success in Québec's English School : Implications for Policy and Practice - Advisory Board on English Education (2011)

Community NetLink - Community Health and Social Services Network (CHSSN) (2011)

Community NetLink - Community Health and Social Services Network (CHSSN) (2011)

East-Island Network Newsletter : Reisaction - Réseau de l’est de l’île pour les services en anglais (REISA) (2011)

Membership Socio-demographic Attributes 2010-11 - Voice of English-speaking Quebec (VEQ) (2011)

Brief : Submitted to the Federal Parliamentary Committee on Palliative and Compassionate Care by the English-speaking Catholic Council - The English Speaking Catholic Council (ESCC) (2010)
The English Speaking Catholic Council acknowledges with deep gratitude the invaluable contribution of the principal authors of this brief: Dr. Ramona Coelho, a family physician who works at CLSC Metro in Montreal. Her training included a focus in palliative care. She spends half of her practice caring for disabled and frail elderly persons who are homebound. And Daniel Cere, Ph.D., Professor, Faculty of Religious Studies, McGill University, and member of the Board of the ESCC. The English Speaking Catholic Council is pleased to present this Brief to the Federal Parliamentary Committee on Palliative and Compassionate Care.

Training and Human Resources Development Project : Final Report - Dialogue McGill (2010)
McGill University’s 2004-2008 Training and Human Resources Development Project sought to contribute to improving English-speaking Quebecers’ access in their own language to the range of health and social services offered to the general population. The 2004-2008 Project was funded through Health Canada’s program to support Quebec initiatives for improving access to health care and social services for English speakers. It was sponsored by McGill University’s Faculty of Arts and administered by its English and French Language Center in conjunction with its School of Social Work. The budget allocated for the 2004- 2008 period was $ 11,757,828. The project had two objectives: to ensure effective communication between English-speakers and the health and social services workers serving them and to increase the participation of English-speaking professionals in the Quebec health and social services network.

Evaluation and Rating Report of English-French Guide to Human Services terminology / Guide français-anglais de la terminologie des services à la personne - Lexicon Evaluation Committee; Harrison, Sue (2010)

Youth Employment Services Celebrates 35,000 Served, 15 Years Strong - Youth Employment Services (YES) (2010)

Collective Rights and the Declining Vitality of the English-speaking communities of Quebec - Leith, Linda; Macleod, Roderick (2010)

Service Offer : Jeffery Hale Community Services - Jeffery Hale - Saint Brigid's (JHSB) (2010)
Jeffery Hale Community Services (JHCS) has a delegated responsibility to offer primary, CLSC type services to the English-speaking population in the CNR, as well as support a coordinated, consolidated service offer for this community. Through alliances with community partners, we work on ensuring the development and vitality of the English-speaking community. JHCS provide youth and family services, mental health programs, and for seniors, home care and a day centre.

Strategic Plan : 2011-2016 - The English Speaking Catholic Council (ESCC) (2010)

Coasters Association Inc. Presentation to the Standing Senate Committee on Official Languages - Coasters Association (2010)
The Lower North Shore, with a total population of less than six thousand, consists of fourteen (14) isolated communities, twelve predominantly English speaking, two Francophone communities, and two Montagnais reserves (Five municipalities.) These communities are spread over 550 km on the North East coast of Quebec.
Keywords: Official Language Minority Community (OLMC)

Collective Rights and the Declining Vitality of the English-speaking Communities of Quebec : Brief to the Committee on Culture and Education with Regards to the General Consultation and Public Hearings on Bill 103, An Act to Amend the Charter of the French Language and Other Legislative Provisions - Quebec Community Groups Network (QCGN) (2010)
Our brief deals with the declining vitality of the English-speaking communities of Quebec (ESCQ) and the relative strength of the Francophone majority. The QCGN‟s goal is to demonstrate that our minority communities are not a threat to the majority, but a constituency that strengthens Quebec society. We expose the detrimental effect that Quebec's habit of emphasising an exclusionary notion of its society has on its minority population. Finally, we seek to attain official recognition of the historic and ongoing contributions our minority makes to Quebec society and achieve legal protection of minority rights and freedoms.
Keywords: Official Language Minority Community (OLMC)

A Consultation - Quebec Federation of Home and School Associations (QFHSA) (2010)
The Quebec Federation of Home and School Associations Inc. welcomes the opportunity to present this consultation brief to the Standing Senate Committee on Official Languages.
Keywords: Official Language Minority Community (OLMC)

A Brief Presented to the Parliamentary Committee on the National Assembly on Bill 103 An Act to Amend the Charter of the French Language and Other Legislative Provisions - Quebec Federation of Home and School Associations (QFHSA) (2010)

Association for Canadian Studies (ACS) and Quebec Community Groups Network (QCGN) Launch Canadian Diversity Issue Exploring Deep Diversity of English-speaking Quebec - Quebec Community Groups Network (QCGN) (2010)

Community Health Education Program (CHEP) : 2009-2010 - Community Health and Social Services Network (CHSSN); McGill University Health Centre (2010)
The Community Health Education Program (CHEP) is a dynamic program that facilitates distance community learning of health and social information for English-speaking Quebecers in remote communities, via five different components: videoconferencing, telephone conferencing, videoconferencing Session DVD’s, community radio (Internet access), follow-up activities (face-to-face)

The Twenty-Ninth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2010)

Roadmap to Canada's Linguistic Duality 2008-2013 - Donnelly, Robert (2010)
Remarks to the Standing Committee on Official Language
Keywords: Official Language Minority Community (OLMC)

YES Montreal Kicks Off its Summer Job Campaign : Close to 1000 Available Positions - Youth Employment Services (YES) (2010)

Baseline Data Report 2009-2010 : Demographic Profiles of Quebec's English-speaking Communities by selected CSSS Territories - Pocock, Joanne; Warnke, Jan (Community Health and Social Services Network (CHSSN), 2010)
This document presents selected demographic characteristics of the English-speaking population of the CSSS territories in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI) of the Community Health and Social Services Network (CHSSN). The information presented is drawn from the 2006 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec's official language minoritty community.
Keywords: Official Language Minority Community (OLMC)

Socio-Economic Profiles of Quebec’s English-speaking Communities: Companion Report to the CHSSN online table series - Pocock, Joanne; Warnke, Jan; Carter, James (Community Health and Social Services Network (CHSSN), 2010)
The Companion Report to the CHSSN online Socio-economic Profiles explores the current situation of Quebec’s English-speaking communities with respect to three related social determinants of health namely, income, employment and education.

The Official Languages Act and the English-speaking Community of Quebec : Learning from the Past - Donnelly, Robert (2010)
Keywords: Official Language Minority Community (OLMC)

The Official Languages Act and the English-speaking Community of Quebec : Looking to the Future - Johnston, Nicola (2010)
Remarks to the Standing Committee on Official Languages

Educating Today's Québec Anglophone - Advisory Board on English Education (2010)

Educating Today's Québec Anglophone : Brief Presented to the Minister of Education, Recreation and Sports - Advisory Board on English Education (2010)

With the Help of YES, the Creative Workforce Turns Passion into Profit : Premières To Showcase Emerging Artists - Youth Employment Services (YES) (2010)

Community NetLink - Community Health and Social Services Network (CHSSN) (2010)

What is Bill C-32? - English Language Arts Network (ELAN) (2010)
Bill C-32 is officially known as the Copyright Modernization Act. It was an attempt at a “Balanced Copyright” act introduced in Parliament on June 2, 2010, by the Conservative Party — Honourable Tony Clement, Minister of Industry, and the Honourable James Moore, Minister of Canadian Heritage and Official Languages. It contains changes to Canadian Copyright Law that are hotly contested by artists and authors of cultural media. The Bloc, NDP and Liberal parties are opposed to the act being passed in its current state, and are calling for amendments to be made.
Keywords: Official Language Minority Community (OLMC)

Building Leadership in Rural Quebec Project Toolkit - Palmer, Lise (2010)

Community, Commitment, Cooperation, Celebrating our Past, Building our Future / Communauté. Engagement. Collaboration. Célébrer le passé. Bâtir le futur - Quebec Community Groups Network (QCGN) (2010)
Keywords: Official Language Minority Community (OLMC)

Assessing the English-speaking Community's Capacity to Access Arts, Culture, and Heritage in Nine Regions of Quebec : A Report on Phase One of the "Enhancing Access to Cultural Expression" Project (EACE) - Quebec Community Groups Network (QCGN); Palmer, Lise (2010)
In 2008, the Quebec Community Groups Network (QCGN) Board of Directors passed a formal resolution to prioritize the development of the Arts, Culture and Heritage sector. This area was prioritized by a majority of members in the Network and was supported by the Board. An Arts, Culture and Heritage working group was created to develop a policy framework in this area to streamline and guide the activities of the Network. The main partners in this endeavour were the English Language Arts Network (ELAN) represented by Guy Rodgers, the Quebec Anglophone Heritage Network (QAHN) represented by Kevin O'Donnell and Dwane Wilkin and the QCGN represented by Sylvia Martin-Laforge. Jane Needles also participated in the working group representing both the QCGN and ELAN. The policy framework, which was completed in November 2008, identified key areas of intervention over the next five years to support the dynamic growth and development of the cultural expression of English-speaking Quebec. The first was a project to access cultural expression through expanded partnerships. This current project “Enhancing Access to Cultural Expression” is a direct result of the prioritization of access to cultural expression. The other areas of priority included recognition and support through visibility - which is currently being addressed through the RAEV project being implemented by ELAN - and the creative economy - an issue yet to be addressed.